OPTIMIZING LISTENING EXPOSURE IN LISTENING REPORTS: A CASE STUDY - Munandar, Aris (Diksi, 2015)
<img src="data:image/png;base64,iVBORw0KGgoAAAANSUhEUgAAAcYAAAIICAIAAAB7CtknAAAgAElEQVR4nOy9eTxV2/8/vpOkwdRAuika1NVgSiFp7mpAJCmzSsmUrlLIkCKUqSgyZsiUIUVkyiwaCMk8HDOdODgH55z9++P1u+t73lS3+/70vrfe7/P8w8PZe+211l57red6rdd6rdcLw5lgggkmmPhOwP7pCjDBBBNM/PeASalMMMEEE98NTEplggkmmPhuYFIqE0wwwcR3A5NSmWCCCSa+G5iUygQTPzfodPo/XQUm/h+YlMoEEz8x6HQ6jUaDv/90XZjAcSalMsHEz47BwcE3b97U1NSMj4//03VhgkmpTDDxk4NMJre2tnZ2dlKp1H+6LkwwKZUJJphg4vuBSalMMPFzg06nM3WpPw6YlPpNYG6qMoGAOsMP0ivof+CfrggTOM6k1D8FlUodGxtjigBMAEAeHB0dHR0d/afrwsSPCCal/gmGhoaYin8mJqGpqamuru6frgUTPyKYlPonYFIqE4yA9XVvb29XV9c/XZf/XdDpdCqV+mPqOpiU+iegUqkUCuXH/HhM/P2Ahf/4+PjExMQ/XZf/XZDJ5L6+vh9T0PnLlPq/qQj/H3zlnx3/oU0bxjynZk5nwGcTMPFdMDw8TCAQfnpK7e/v7+jo+M9VhQkmviP+fruiqQzOpNT/ECYmJkZGRn7M5v0LlFpfX//q1av/XFWYYOL7gkajdXR0fPr06e8pDii1r69vYGCgp6entLSUqRz4H8Rfk1IJBMJ/rio/Pj670PtHavLDYqqY9m830f+9bWk0WnNzc39//99ZbldXV09PD4FAyMrKYh66/x/ET6NL/ZJq7CsXGXVe/6E6gxMgxnK//cHvXpmvMP6fVuwba/4tGf6D2vb/S9FUKvUrLp0m5Tw+Pj4wMNDf3z88PIwuTkxMTHqWRqORyeRJWQ0ODg4NDQ0ODpJIJLgyOjo6ODgI1+HWx48fJyYmJiYmBgcHiUQiuot+Dv2BwcFBxiKmDpPBwcH+/v7+/n4ikfiVz/fhw4eioqL6+nr4OTIyAqX39/d/+vQJCoJXHhsbm5iY6O7u7u3tHRoa6uvr6+3t7evr6+vrQ1Xq7e3t7e0lEolEIhFpPGGbvqqqqq2tbWRkBKWESaijo6Orq+vHVI/+Jfx8O/50Op1EIpFIpKm21hMTE2NjY4xXJv0EUCiU4eFhyIFCoVAolNHRURKJNDw8PDo6SiaT6XQ69HIymUyhUMhk8sjIyMjICHqKTCYjAQSNIuimNBptZGQEnhoeHh4aGvr06ROJRIKsKBQK9CQwAYGiR0ZG0BtBGigREg8NDaGLJBLp06dPKEMymcw4hmk0Wl9fX1tbW2tra3t7++Dg4KQX7+7ubmxsfPfuXWVlZXt7+9DQ0PDwcH9///j4OOMYo1Kp/f39jY2N7e3tBAKBQCA0NTU1NjYyrqDpdPrw8HBTU1NTUxOkaWtrq6+vb21thdUuiUR6//59YWFhSUlJS0tLT09PQ0PD2NgYnU7v7e1tampqaGhoampCRTQ3Nzc2NjY3N9fW1n769Km3t7ekpKSysrK5uZlAINTW1paVlZWWllZUVLx//76lpYVEInV1dZWVlb19+7aioqKmpgbel0ajUanUzs5OuFVeXg71Ly4ufvPmTWVlZWVl5evXrysqKmpra9+8efPq1avKysrc3NynT5+iZmxvby8vL4e7tbW14+PjqJ17enoKCwvv3bvn4uJy8+ZNd3f3x48f19bWFhYWvnr1amhoiLHBR0dHk5OTk5OTy8vLKysr37x5Ex8fb21tfeXKFTs7O3d395qamomJidraWj8/v+vXr7u5ubm5ubm4uNy7dw9IMC4uzsXF5dq1a7dv387IyHj27Jm3t7erqyukvHbtmo2Njbe3d05OTmtrK2M/hM+dkZFx7do1T09Pb29vZ2fnyMjIqqqqkZERxmSdnZ0xMTGGhobKyspGRkYxMTEZGRkPHjwYHh4uLy+/d++em5ubu7u7q6vrzZs3k5KSent7R0dHnzx54uPj4+LicufOnaysrOzsbD8/P6iVu7t7QEAAPOjo6BgZGYlWt2NjY1euXLG0tPT09HRzc7t165a/v394eLivr++FCxdMTExKSkp+dm3Jz0SpIyMjTU1NT58+vX//flBQ0IMHD8rKyhjHeWtra05OTk1NTVdXV3d3d0dHR3R0dFFRUW9vL+pGnZ2dYWFhvr6+ISEhISEhwcHBwcHBISEhYWFhISEhfn5+wcHB3d3dr169CgwMDAoKCg4ODgwMjIiIePHiRXFxcXx8fFBQUGBgYGRk5KtXryZNqlQqtaio6N69e/BUVFRUXl5ecnJyaGgoyur+/fs5OTnj4+P19fURERFQYnh4eERERFhYWHBwcFBQUFBQUFZWVktLS15eXkhICDwbHBwcERERGxsbFxcXGRkZEhLi7++fnJyM9gzHx8cfPnyor6+vpKR07ty54uJiVLH+/v6srCwjI6Pjx4/v2bNn69atxsbG7u7u3t7ely9fnqTPGR0dTU1N1dfXP3z48JEjR44cOXLs2DFra+uXL1+iNHQ6vaamxtHRUV1dXU1N7ciRI+rq6gYGBrdv34a5xMvLa9u2bStXrly3bt3JkydPnTq1c+fOnp6ejx8/WlpaKisrnzhxQldXV0NDA57V1tY2MDDQ1tZevXp1eHh4SkrKkiVL5s+fv3379iNHjigqKgoLC/Pz84uJif36669Hjhx59+7dw4cP161bx8HBMWfOHEFBQTc3N2C00dHRhw8frl27louLi5eX19/f//r16wICAtzc3HPnzp07d+6CBQv27dtnYmIiJyfHw8Mzd+7c2bNnS0lJIRXB3bt3xcTEeHh4FixYYGJiQiQS4ZXr6uoMDQ15eHgWL16spKSkra29YcMGISEhcXFxYWFhBweH3t5expYcHBy0srLauHHjvHnz5s6dO2/evF9++UVAQEBAQICPj4+dnV1HR4dAIFRWVioqKs6aNYuVlZWNjW3OnDknTpzo6enp6+uztrZesGDB7NmzDx06FBERERMTo6Ghwc3NzcbGxsbGNm/ePHgvDg6Offv2lZaWQoek0Wg1NTW6urpz584VEhI6derUmTNntm3bxsXFtXbtWj8/P5h+6HR6T0+PgYEBPz//2bNnw8LCDA0Nly9fPnv27E2bNg0NDdXU1Fy+fHnJkiVQ3ObNmx8/fjwwMECj0crKyo4ePTp37lxDQ8O6urp3794ZGxtDsjlz5tja2jo4OOzZs2fBggXs7OyqqqoNDQ1A4tnZ2fv27WNnZ2djY1uxYoWDg0NcXJyjo+PBgwc5ODjOnz8/qQ1/OvzolIrm0g8fPly6dGnFihVr1qxRU1PT0dGRl5cXEhIyMzN79eoVCBFVVVXW1tbbt29funTp0qVLN23atHHjRkFBwfXr1zs5OcFixMLCgpeXd/Xq1RoaGqKiojw8PDw8PGvXrj19+vTRo0d5eXm5ublTU1MLCgqOHDmyaNEiHh4eXl5eFRWV2NjYoqIiW1vbFStWcHNz8/Dw7Nixo6SkhLG2hYWFe/fu5eLi4uHhWbJkiampaW5u7uPHj/fv3w8FzZ8//9ChQ8XFxUNDQ05OTkuWLFm2bJmysvKFCxeMjIygPtzc3IsWLbpz505LS8vLly8NDAx4eXl5eHgEBAQMDQ2joqLi4+MtLS2FhYW5ubkXLFhgZGT08eNHaKuSkpIjR47MmzfP2NgYEWVZWdnOnTt5eXlFRERsbW1DQ0N9fHzOnDmzYsUKLi6uhQsX1tTUML4FjUbr7e11c3Pj5ORkZWVlZWXV0dF5+/YtTEsIFAqlublZS0trxowZrKysK1as8Pf3B5nX3t5+3rx5Z86cqa6uLi0tvXDhAgcHx+LFizs6OkpKSoSFhffu3RseHn7p0iUhISFWVlYODo6TJ0/6+/ubmppOmzbNxsZmaGjI19cXwzAMw+bMmXPlypWAgACQZXh5eTdv3tzR0UEkEjMzM3/55RdIxsHB4eLiAh2GSCSmpqby8vKeOXMG1pVhYWErVqyAlPDhOjo6MjIytmzZAhfZ2dktLS2BawYGBp48ebJp06YjR450dHQATxUXF2/evJmNjW3ZsmX+/v4EAqGzs7OxsTEpKenXX3/FMMzCwqKvr29SS3Z1dd26dWv+/PkYhm3YsCEyMhLE86SkpFWrVm3ZsqWysnJsbCwrK2v79u1Qk7lz5z548ACEtbCwMCEhocOHD9fX1w8NDZFIpKamplWrVkFKc3Pzuro6AwMDDMNYWFgUFBRaWlpwHH/58qWysvKMGTOWLl0aHh7e2dnZ3d3d2tqqrKyMYRgfH5+vry+O4yQSyc3Nbf78+WpqaiCM9/X1RUdH8/Pzr1y5cmhoCK7Iy8tDcUePHh0ZGYGxNjo66uTkJCcnFxsbS6VSx8fH4+LisD+Qm5s7MDBQUVGhoqKCYdj06dPV1dVhWTk+Pn716tW5c+diGLZ379729vaRkZGBgYGmpiYlJaXz58//7GZFPzql4n8whYKCAgcHx9y5c21tbauqqt6/f5+RkSErK8vJySkqKgqrtpGRkdevX584cQK+q4mJSVFRka6uLoZhPDw8xsbG2dnZBw4c2Lp1a0pKSnV19Z49e9AY+/DhQ1VVVUBAACcnZ2Ji4tDQkLe394IFCzAMmzdv3p07d3p6ekgk0uPHj1GHZmVlvXTpEuOS2cbGhoWFBe6uXr36/fv3Q0NDRCLRzMyMlZUVw7C1a9c+evRoeHi4r69PW1tbUlIyNDQUlrdBQUFQHIZhW7ZsqaioGBsbGxkZ8fPzW7hwIYZhCxYsuH//fl9f38ePH5OTk1evXg2JOTk5nZycoAIUCsXf33/Hjh3BwcHQ9cvKyuTk5DAMW7hwYWRkZHd3N+g0Wlpa4uPjRUREZs6cWVFRwdja8EaVlZXc3NxQhJ+fH7o76et4enry8PBgGCYiIpKbm4vjeHt7+9q1a9nZ2R8/fgxpWltbjYyMli1b1tLSkpOTs3///tDQ0OHh4adPn4qIiGAYNnv2bF9f34GBgfb2dmlpaRMTExzHs7KyENkVFRVRKBTQYDo7O+/cuRPJ4IaGhjNnzoSUK1eufPjwIVwnkUgiIiLR0dHws6ysTEpKCnKzs7OjUChw/eLFi4gI+Pj4goKCQDVZV1d36tQpT09PSFZfX79//35I5uXlhR4HlJaWioqKmpmZfVbCun79OjSRsrJyU1MTXJyYmPDx8VFVVS0tLcVxnEajxcfHr1y5EsOwGTNm7N279927dziOm5iYaGlpAVEiSEhIQE2cnZ1xHE9KSkJzT0VFBZlMNjAwgP5maGjIuEUWExMDRWzduvX169ddXV1HjhzBMExGRgZpUel0uo2NzapVq0A2x3FcUVER8j9x4gRjP0lJSdHR0cnIyIAr6HuxsbGhHuXg4ICGA9Ide3t78/LyYhimp6eH4/jY2FhFRcX4+Hh8fDx00alt+BPhJ6DUjo4OBQUF+DCWlpYgkQHCwsJgutPU1GxsbMRxnEwmOzs7Q7/09/fHcby0tBS64KpVq5ydnS9duoRGnaamJpp+4QqJRFJRUcnLy8NxPDExEfqfpKQkWhKWlpYqKysLCgqC3LF161bU8/r6+vT09BYvXrxo0SKgRVRPZ2dnGFR79uypra3FcZxAIBw/ftzT0xO0vWNjY/b29kANgoKCBQUFiLxAnMEwbNmyZYikysrKdu3aBeIhhmECAgL3798HDs3NzdXT04uPj8dxvKWlRV9fH8OwadOmOTg4TNUsBwQEcHNzw6hGgHwIBAIfHx+0T2RkJD5lLw4QFBS0ZMkSDMOkpKTevXtHo9FSUlLmzZs3c+ZMGxubgYEBSFZQUHDo0KH29vZXr155e3u/f/8ex/H8/HxxcXEMw7i4uMLCwiDzxMTE9PR0HMcfP34MpXNwcECjPX78+OXLl69fv7a3t4ccxsfHL1++rKCgAEMUqgGPA6VCO+A4/uLFC+gGHBwc9+7dQ4r4y5cvL1y4UFJSEo18+PqDg4NOTk5eXl44jg8NDbm6usLXWb58OSSAuQfpWG/fvu3u7j6J+3Acp1AoZmZms2bNAkolEAgtLS2+vr6FhYXV1dWZmZnoYOvw8PC1a9dmzJiBYRgLC4uGhoaJiYmDg8OkNQSZTBYTE4PaWltbwxdHc/zbt2+fPXsmICAAVYUPh4DmV5hXenp6tLW1WVhYZs6cuWvXrtDQUGiW7u7u7Oxs1FvQXGJmZsbYSbKzs3V1dZ88eQJXnj17Bsnk5eUbGhrgopubG/ouaCvv1q1bICWcPHkSx/GqqiozMzMCgQC7YZ/d//iJ8KNT6vj4+KNHj+bMmQMySFZWFuPd1tbW5cuXgwQHvYdIJMLEOGPGDC8vLzKZTCAQYJrl5uY+d+7c+/fvEQkePXoUvreamhoqrqSkBAg0NjYWMpeTk0Ml5ufnGxoaHj9+XFZWFsMwISEhVKWIiIgLFy5oa2sLCgpiGCYtLY00rR4eHkBPO3fufPv2LY7jw8PDubm5aG0eHR29bNkyIJdbt24xvmNcXBwwu6ioKNqCKCgo0NTU1NfXR4L2+vXrIefi4mJTU9OkpCQcx7Ozs0HSnDNnTllZ2dTm7erqunr16lQiwHG8paUF8dSDBw++9IH8/f0XL16MYdjevXuHhobodHpFRQVI0Pz8/AYGBo8ePYLVdFlZ2ejoKJFIbG1thdGVm5uLKDUkJAREv7GxMRCsEKVycnI2NTWNjIyYm5uHhYUNDQ01NjbCwBsZGfn9998dHR3t7e3XrFkDk4eCgkJTU9PQ0ND69etjYmKgnohSubi4goODkZhpbGy8f//+uLg4pEDYunVrdXX1p0+fLl++DFJqQ0ODtLQ03NXR0YHJmxE0Gq2np6e+vn7qliCVSg0LC4OPe/To0d7e3ujoaBERkfDw8OHh4UlTVFtbGyyqMAwDmisvL4dbKCWi1MWLFyckJOA4HhAQAI+sXbu2oaHB2NgYJloZGZlJiqmXL19Cv8UwTFFRkUKhxMTEoLXR8uXLtbW1g4ODJ238Ikq1srJCF+l0+vPnz3V0dKZS6vr160HSLCsrO3jwIDC4s7MzkpcRpSopKT1//vzkyZOSkpKf7YQ/I350Su3v7z9x4gQICFpaWmj2AwwODgoLC8OHNDU1hf1xRKmBgYE4jpeUlEAXFBQUjIqKYnx8KqUyAlGquLh4W1sbXARKDQ4Otre3B6oyMjICgeXIkSMBAQHOzs4gODNSamRkJCjyEKUyorKyEphx5syZ6urqjGI4zkCpGzZsQMtGqEZSUlJmZua6deuwP9RVDQ0NoLtMT08fHx/38PBArPThw4fPtvCkTWqEv0qphw4dgit0Ov3y5csgbWEYtmbNGkNDw+Tk5KnPfpZSEZKTkyGHOXPmuLm5WVhYrF279v79+4xphoeHL1y44O7u3tbWdvXqVSh05syZ1tbWHR0d4uLin6XUoKAgVJahoaGOjs74+Li7u/u0adOgxJMnT6anp1+4cMHb2xvH8Tdv3nBycsItW1tbNCV/C2g0WkxMDHSk1atX6+jobNq0aeHChXFxcZ9NX15eLikpCeojWVnZqqoq/F/XB4hS+fj4jh07ZmpqumrVqmnTpomJiT18+HB4eHjv3r1QVTk5udevXzNm3tPTc/jwYbi7Z88eHMcHBwcvXLgAPRawePFiExOTwsJC9BSiVCMjI3TxK5QKQ9XOzm7Pnj2zZs1as2aNh4cHo4YUUaqQkJC8vPzcuXMPHDjws+9KIfzolEogEGCpgmGYpqYm0vgABgYGkGbz8OHDYO8GlDp9+nRdXd3AwEAQUVevXu3j44PWoYCplMpo04coVUREBHXNvLw8PT29nJyc3Nxc6BZr1qz58OFDTU3NgQMH8vLyQO0AMgIyB0lJSVm7du0kSoWCJiYmLl68OHv2bAzD1q1b9/z580ktEBcXB3QsICDw6NEjuJifn6+vrw9CSmBgIBI0TE1NY2Jibt26BbYQRkZGcJ2Dg6O6uhqepVKpAwMDjLxAoVCmrrb+KqUqKSmhi42NjXp6eoiGMAxbunQp2OUwPvt1Ss3IyODi4gKKVFFRWbly5dy5c2GaRBgeHtbS0rKxsSGRSLW1tVpaWrDEFhAQcHR0/PXXX9GA/xKlnj59WkVFBcfxT58+6ejoTJ8+HcOwuXPnHj16VFdXF7ZxysvL0YtYWVkhLVBvb29GRkZBQUFRUVFRUVFubm5BQcEkVeDExISXlxesUXh5ecXFxRctWrRw4cKYmJjP2mBSKBSkf8Qw7NKlS8A1UymVlZV13bp1Bw4cUFdXv3TpEjICO3DgADy7devWN2/eMGb+6dOnY8eOwd2dO3fCxb6+PhcXFzk5OeiEgIMHDyIxAlHqqVOnUFZ0Oj0zM/OzC392dnYpKSmU2/Hjxye9I6JUMTGxixcvHjp06ODBg52dnVNb42fEj06pnZ2daNZVUlJi3EjBv0Cpjo6OcEVERGTfvn3y8vIHDx6MjY2dmvk3UqqEhASaQvPy8vT19VNSUggEAvRObm5uOzs7CwsLBweH7u7uK1euIEpFYyY8PByymiql5ufni4qKYhjGxsZ2/vx5ZLYNdtE4A6Uy6lKBUmHvpaen5/LlyyBogLWNr68vgUAgkUjnz5+fSqmfPn2KjY29evVqfHx8dnZ2RkZGWFjY1HNxX6FUsKgFVgoICJhEqVDtxsbGK1euSEpKIglISEgoJyeHkUe+TqmlpaUggM+aNSssLCwoKEhZWRltNwFIJJKSktLFixd7enpwHK+trUV7KTNnzpw3bx7smOFfpVRVVVX4v729/dixYyCrsrKyrlq1KigoCMfxyspKNGlZW1ujZUR1dbWmpqasrOzmzZs3b968Z88eR0fHSapPOp0eFxcHX3/79u3p6emurq4rV66Mj4+HGReOGKD0Hz58OHXqlLCwMAiqfHx8/v7+jI2GKHXJkiVIU8wIExMTNjY2DMM2b94Mal+E8vLyrVu3wosoKiqOjo7W1dXBPPf27duLFy9KSEjAipCbm9vHxwfKBUplZWW1tbVFWdFotLS0tOPHj6ekpMAVRKmSkpLv3r27du0aTG9SUlI5OTmM1UCUChz9/Plzfn5+aLePHz+SSKQvnev5KfCjUyrs+YBuSF9ff5LChUgkIkrV1NTs7u4eHh4GSmVhYbG2tp5k1DIJ37jwZ1zCg5QKXTk0NJSNjQ3GnrCwcFpaGs6wg8wopV67dm3evHlTKZVIJGpra7Oysk6bNm3Xrl1oF5tKpX748OHdu3dUKjUhIeFLlIpWtR0dHXp6emjdevr06d7eXjqd7u7uDlc4OTlhBxkKDQwM3LhxI9xiYWHR0tJCKgWEr1Dq6Ohoeno6cPT9+/cZKRWMN1+/fg0DtaamxtLSEhQX7OzsjBtW+J9Ran5+Pmil58yZA+tfR0dHqElfXx8YyY6OjhoaGjo4OKBNnrS0NFgQANB+9Jd0qadPnz58+DAqtLW1FdkMCQgIBAcH4zje3d2NVJxmZmaorLGxMbRNj2GYsrIy1HMSHWRmZoKV1caNG4uLi9+/f29tbQ3yY3V1dVlZGdLAdnZ2XrhwQVlZOSIiQlpaGlh1x44djPuHiFKFhIQ+S6lIzwCbloy3SktLQZfKycnp4eHR0NBgaGiYmJiIOmp5ebmKigorK+uMGTMMDQ3BbA5kmtmzZ1+/fp0xt5CQEHV1ddgMxBko9cCBA+3t7c3NzUi83bVrF+NM4+HhAV1LV1cXx/Ha2lptbW1oVX9/f9ic+Oxe6E+BH51Sh4eHPT09QdJZv359ZmYm410kpbKwsNy8eZNGo3369AnpUr29vaceB2TEN1KqjIwM+rogpYLMW1FRAcNv2rRpenp6IOhZWloiSkVEfP/+/aVLl06i1ImJCRcXFxB/VqxYERUVhaQVCoXi7Ozs4+MDZlswaCdR6okTJxhF79LSUjASwjDM0NAQllHPnz8HcWDWrFmo6eCUZHh4OJLmkIk4I1pbWxGlhoeHT7qlpqYGAmBgYCBs7AClUqnUuLg4XV1d9JoUCiU8PJyHh2fatGnq6uqMOrXc3FxEc6GhoZMoNS0tDSQmDg4O2N9PS0srKirCcTwxMVFRUZFGo01MTBw8ePDixYto7qTRaKmpqYjmEKXm5eXBtj5IqWirxMjIaNLXz8jIAM765ZdfgFLBjAFsNiQlJaEOgPb2diUlJSjr/PnzoBOYRKm5ublgK6aoqAgW77DoGRwc1NLScnR0hMqPjY3dvXtXQUHh/fv3VCo1JiYGdvlYWFhOnz6NRGMqlQrz0PTp0318fPApaGlpUVVVZWFhmT59+rlz5xhvBQUFwUbZvn37uru7m5ub1dXVDQ0NGSWVp0+f8vDwcHFx3b59G3oFekFdXV3UT0gkkomJiYmJCRhj4AxGVEJCQhDyICIiQkhICKqqra2NXsHT0xO6vYqKCrD22NjY2NhYY2OjgoLCvXv3cCal/udAp9Nfv34N0sqMGTNgIYbw4sULEJFkZGRgjfPp0yeQUmfMmHH79u1J1un4v/p809DQ+AqlohW3tLQ0egTEQ9hbIJPJnp6eUNaTJ0+gB1y4cAHylJWVZSRi4I6dO3dWVlbCxbq6OpCnWFhYzp8/z0hqNTU127Ztc3Nzw3E8OTkZSalIb1VQUICYHUCj0QoKCmDAGBoaAnP19vai+lhbWzNKiKmpqXB97ty5k3auoNqtra1AxxiGhYWF4X8YV1Gp1OjoaAEBARCd/P39+fn5QRKBLezw8HB+fv6AgAD0+hUVFaKiorNmzUJ7O5DVixcvQOnByckZHBwM+lw0lvLz8+F1Zs+eDTLd8PDwyMgIgUCwsrJSVVWl0+kTExOnT5+2s7OD+QyyHRkZuXnzJtAxkqFevHgBRMnOzu7k5AQH3mk02qlTp1RUVOgM7k2pVGpERMTy5cvnzZuH+ltfX5+mpiYbGxsLC4u7u/vExAQkbmtrA/t5DMOsrKwmKevxPxbIsD/G4vMAACAASURBVIkqLy9fUFBApVKpVCqJRPLz85s3b96DBw/Gx8fHx8d9fHwkJCS8vLzgLSgUypkzZ5Bu197efnx8nEqlDg4Ogj4EwzAbG5upcyGNRispKfntt99ACsnOzgaH2V1dXXv37mVhYVmyZAkYGhMIhAMHDsARif7+fvBREBsby8rKKiMjg+TKu3fvgkCwYsWKyMhICoVCIpHu378vISFx//59eGp8fBxtJ7KyshYVFcHJbCsrK5C12dnZzc3N+/v7yWTy77//DhuJ69ate/r06djYWEdHx/3797dt2yYmJvbs2bOpg/Enwo9OqTiOUygUHx8fGN6GhoZIrfnp0ydNTU34YPfv3wfLj6GhIaBUVlZWOBw5KTdGCeLrlPro0SOYY9etW4cCDRUWFqqoqADF4DheWlq6atUqUVFRZIqAKExGRgZlFR0dDbS4Y8cOWIATicSTJ0/CUn3nzp3orOfExERKSsru3bvZ2NhglzwsLAym9KVLl6ItiNTUVGlpadg8YXw1X1/f+fPna2pqAqXS6fSqqqp9+/ZhfxxYQA0SFhaGpFSkE2DE27dvkam/lZXVy5cvc3Nzs7Kybt++vW7dOnZ2dnjK2toaPsHq1auzsrJgg5uLi2vJkiWhoaHADmFhYfPnz1+9enV1dTXtD8BbgAXljBkzLl26BLYH6PiTs7Mz0CILC8vFixczMjLi4+NtbW23b9/+yy+/XLhwYXx8/MWLF2vXrt22bVtCQsKnT5/Qx+3o6Dh27BgLCwvI9SQSyd/fHyZmYP+4uDg4OiwsLCwpKZmamtrQ0IDoaXR01NbWVkRE5O7du6hBGhsb7ezsODk5FyxYoKurGxcXl5ub6+XlBUsZNjY2d3f3SftvVCo1OztbUVERmHHmzJnbt293cHAwMTGRlJSEz/r8+fOKigp1dXUeHp7p06efOnUKWqm9vR3s8AELFiywsLAICgoyNDQEHSUw5sOHDz8rN+Tl5R06dAi0UidOnLC0tJSVlZ02bdrGjRtjYmJAYGxvb4e9LC4uLkVFRUtLy3Pnzm3atElMTOzx48eoNYhEoqOjI3QGPj4+CQkJUVHRbdu2BQQEwBTy4cMHGxsbRPQYhm3cuBGsv1tbWw0MDKCfz5kzR01NTU5ODvUrDMMEBATExMTWrFkDmjEdHR20LfaT4kenVBghQ0NDHh4ewsLCs2bNOnz48M2bN69du6ajo8PCwrJixYrr16+D7NPS0uLj44OOGIqLi8OpJ5xhwxT9ExERAeIVhmG8vLxnz5718fFBFnlPnz5F+WAYpqSkFBsbm5iYqKGhwcbGtm7dOn9/fyKR2NbWZm5u7uLi8vHjx87OzuDgYFjiARHo6+uHh4e7ubkhowXYPrp7925UVBQ688PNzS0rK7tjx44dO3bIycmhWqWnpz98+BDUcAAxMbErV644OTlt2rQJw7BffvnFzc2N0fpkaGjo7Nmzhw4dQkYwdDq9srLy+vXrkpKSixcvRgUJCQlxc3Pv27fP2dl5qmxVVVUlKyv766+/wvhRVFQ8deqUvr6+jo6OgoLC+vXrdXR0qqqqQkND4aeoqKiUlNSZM2eSkpKePHmioaGxb98+DQ2NAwcObN++fevWrRoaGshcAYgvKytLW1t706ZNoqKiYmJiBw4cuHTpEph8fvr0KSoqSkFBYe3atXB39+7d2traampq8vLyy5cv37p164MHD0pKSs6ePbtu3TopKSkLCwvYukTft6am5sqVK3AxJSVFT09PU1NTUVHR1NTUxsbG39/f19f3+PHjmzZtOnbsmKur6/Pnz4FEIIcPHz4EBQVN2t4ZGBiIj4+3srJSVFRUUVGBKunp6Tk6OiYkJLS0tEzyREUmk6OioiwsLIyNjc3MzIyMjExNTR0dHa2srLS1tU+cOHHlypX29vb8/PzTp0+fPHnS2NjY1dW1pqYG3BLeunXr7NmzZ8+edXBwuHHjxrVr1x4/fmxvb3/r1i1bW1tjY2NTU9Pw8PCpnw/eora2Njw83NLS0tLS0tra2sDAwM/Pr6ysDL3myMhISUlJQkJCRESEnZ3dhQsXHB0d79y5g3yXoCmqu7s7PT09MDDQ1NTUwMDA2dk5LS0NBgudTu/v78/JyYmKinr06NGjR4/i4+OjoqKqqqogk5aWluTk5Li4uOjo6MTExLCwsIiICEgZGxsbFhaGXHbExMSAH5lvooYfFT8HpeI4TiKRnj17ZmVlZWBgYGlpaWZmdvLkSRsbmydPnqBZuq6uzsXFxdjY+OrVqx4eHufPn7916xZMepMolU6nh4WFOTk53b5928fH586dOwEBAbAGgWRhYWG///67l5eXj48POPJ58OBBbm5uaGjozZs3PTw8MjIywHPV+/fvIWbDx48fs7Ky7t275+Pj4+Pj4+Hh4evrm5ubm5iYGBAQAAV5e3v7+fmlpaW9fPnS19cXUt68edPR0dHOzs7Ozs7e3t7Z2dnT0zM4OBjcpri7u0M1vLy83NzcoqKiYmNjvby8PD09b9y4kZiYOMm8vL6+Pj09vampiVEeHx0dLSws9PLysre3h4JcXFyio6PfvHkzVcbBcby1tdXNze3Jkyc5OTlZWVlPnz5NTExMSkpKSkp6/PhxdnZ2XV3dx48fs7OzExMTs7KysrKy0tPTnzx5UlZWRiAQ3r17V11dnZaW5uLiYmdnFxISAspQRlRWVsbExDx//hweT0lJiYmJAQuk4eHhly9fJicnw63s7OzU1FQoOi0t7dmzZ6WlpR0dHQ0NDU+fPn327NmzZ8+ys7PRrhF6ayKRCFJ5ZWXls2fPwAVXV1cXPFtRUZGZmZmTk/P69es3b960tLQwLv+h0T7bOCMjI2VlZQkJCQkJCc+ePfvw4cOXAlBPTEw0Nze3tbX19PT09PSAK5/W1ta2tjbw7ANSbV9fX2tra09PT2dnZ1dX1+joKNhUwJXOzs6RkREqldrT0zMyMtLT00On04eGhrq6uggEQldX12eXYuh/EokER7YYrZSm7qfDAQrGGIWf3Xb/9OkTI4N/fV/+J1WG/h/xo1PqVLS1tVVXV9fU1DQ3N0+6NTw83NDQgI4YkUiktrY2UPAxUiosPL/umbilpWXSIg6k3Z8I/54ZCv1vjy/CBBP/TfhpKPVLQ/1biINx9xDyQT+RXu+z+UwtkTGfSem/coXRpyqU/vU6I1/IkJKxGpOe/Wyh8FKMtz5b6Ger8Y01/BYwVgO1MxNM/HfjZ6LUbySFSdenPkifgqmPT/rnSxX4lmr/G/kwpvn3Cp1UytRqTP056fG/VOLXq/Ed82SCiR8cPw2lMsEEE0z8+GBSKhNMMMHEdwOTUr8b/qpm4Evqxc+qHb6S5hvX79+46v9SQV9J8NmDLlP1p1M1vF96HF1kzOGzNQGzebCBZyzoS+ogxjRgYI+M9lG5kCfUEw5owc+vN8JXvgL8nZiYgPhjKJYJ49tNTEyA24SxsTHUUKiSKDFEV0M1R+1J/0NlPzY2BvHywHUA1Pzv0WJDcUyNOZNSvxv+at/90jj8S5T69fzhn97e3hcvXmRmZoI9WW9vb3t7+5eeGh0dffPmTU5OTmlpaU9Pz4cPH/Ly8srKyshk8tjYGNzKzc198eJFXl5eRUUFiUSiUCg1NTU5OTkvXrwoLS1FRjZ0Oh3C2efm5ubk5BQUFLS2thYXF2dnZ+fn5xcUFOTl5WVlZWVmZmZlZeXn5+fn5+fk5CBLjLGxsaamJlRcWVkZo/csKpX6/Plze3v7CxcuXLx48dq1a9HR0Y2NjR8+fEhPT/+sG2PUIMXFxc7Ozmpqart27dLW1r57925tbW1bW1tKSkpxcbGbm5uVlZW9vb29vf3ly5ft7e3T0tK+HrmTSqVmZGTk5+cjx/WMGBkZAQNecXFxeXl5W1vboKAgDw8PFLK0qKjozJkzMjIyEhISGhoa7u7uYIJaW1tramq6detWS0vLq1evWltb6+vrKyoq7t+/X1ZWVlZW1tPTE4z2aTTa27dvwVB/5cqVIiIi2trax44dA6fRf4MWm0KhNDY2vn//nhln+7tR6r+3e/NfBjqdXl5ebmpqqqSkBIHwVFVVf/vtN19fXzs7O2VlZbhoZ2cH/jVwHK+urjYxMVFWVj506JC5uTmyAAO8efPG1tb2yB9QUVExNzcvKipi7Ljd3d3BwcHm5ubq6upHjhxRU1PT0tKKjIwkk8lEIvHWrVsKCgrgr3r79u3m5uZXrlyBszGPHj06fPjwb7/9tnv37oMHD0JUvr17965Zs2b58uVSUlL29vYPHz40NjaWk5NTVFRUVFTctWvXyZMnNTQ0hIWFhYWFpaWls7OzqVTqnTt35OTkJCQkpKSklJSUkLvr169fGxkZrV+/XkpK6urVq9XV1UFBQbt375aUlJSUlNy/f7+Li0tYWJi9vb2UlJSEhIS4uPipU6egccbHxysqKuzt7SUkJHbv3h0SEoIoNTc39/jx42vWrBERETE1NXVyctLR0REXF5eRkdm7d6+joyNqn0ndsr29/fLly5KSkry8vFu3bjUwMNDX19+yZYukpOTevXvPnz//4cOHe/furV69mpubm5ube926dY6OjuXl5V/v2H19ffv27dPT00OGfYzz4pUrV5YvX66goHDnzh1nZ2dFRUUBAQEREREwAi0sLNy1a5e4uLiDg8O9e/euXbu2bds2Pj4+Jyentra21NRUbW1tfn7+efPmLV269Pjx42fOnDl9+jScb/7tt9/g2F5NTY2SktLixYuNjY0DAgLc3Nx27tyJYZi0tPS/25f/GiYmJgYGBnp7e/8Lokb/H8Gk1O8JOp3e0NDg6uoKHuYBhoaGT548iYiIgCNPGIbNmjXLyMgIYru2trbevn2bn59/4cKFvr6+kxzxNjY2enh4wJFHDMMWLVrk6en5/v17xhMmRCIxJSVFXV0dlXjs2LGcnBwKhRIfH8/Ly7t+/foHDx4kJiZeuXIFzkSFhYWNjY1ZWlqysLBoa2tbW1ujui1btsze3t7Y2Jifn//QoUMFBQX37t1D/lMUFRWTkpKio6OdnJxUVVUxDIMjm8XFxSdPnkQVUFZWhiO8nZ2dQUFBcnJycnJy2dnZRCKxqqoKnQfbtWtXaWlpQ0NDenr6hg0b4OL06dPPnz8PnkQ+fvyYkpIiLi5+9OjR0tLSiYmJkZGR6Oho8LEvJCQUEBBQW1vb2dlZVFTk4OAAR9EvXLiA2odRsVBTU6OtrQ2H1oyMjAoLCzs7O+vq6qKiosDZkr6+/tjYWH9//+bNm6EyBw4caG1t/RJN0P/weBsXF8fJycnDw8N4Qgz+vnnzZtmyZfPnz0dH1588ebJ582Zubm5YKxgaGmIMMUhGRkYCAgLmzZtna2sLMm9CQgIc1hQSEnr9+nVnZyeJRHr9+vXu3bt3795dU1MzMjJy69atadOmrV27FvUf8E0uKyv7f+7UTPw1fB9K/Za16n890MJ/dHTUysoKw7Bp06Zt374dLQYfPHiAnIcuXLgQOQrAcVxfX19DQwPlw5htb28vhMCcMWOGgYHBZ9PgOB4REQHhZJYtWwaukhobGyE+5cWLF1GyqKio3bt3BwYGkkik69ev6+rqQvW8vLwgmtbZs2chf29vb3l5+aampqamJvAIt2jRIhTXD8fxjo4Ofn5+FxcX+IkcEcGLW1lZgVDZ39/v6up65coV9CBygIt4hEKhALMAFi9efPPmTTjyTyQSTU1NAwICoJ5ZWVkwXfHx8SUmJjK2AJVKDQgIkJSUNDc3Rwt/9FGIRKKNjQ3kr6CgMGk1UFpaKicnp6WlBec7wCsC9q9+7KcCvkJXV5eCggL4AbGwsICZEm5RKBR3d3cuLq7Fixffv38fUXNMTIyUlBT4Ydi2bRuGYdra2ij+CplMPnv2rK+vLzQg8sQmISEBCV6/fg0uylxdXSH0KbjuFRQUDA0NRafpbt68iToVE38bvhulQtTP/3FKRWPM3NwcBC7w4goJYmNjN2/ejGLkSUpK5uTkwIDX19dHzs8nKWSbmpog7OCsWbOMjY2BWSalodPpOTk54EVfVlYWnLCkpqYKCgqysrL+9ttv+fn5aJD7+vpGREQMDQ2lpKQgLaGTkxOIQhCdFMdxIpFoa2vb3NxcUVEBUhsfHx+EtyOTyUActra2yDlWXFwcDw+PvLw8Ozs7hmFLliwJCwsDB0ig8US++3bt2jWJsCAcjoSExNKlS8EJi5CQEHib7u3tNTQ09Pb2/vjxI4VC+f333+HZ3bt3o+ZCcmhvb6+/v7+XlxcjpcKtp0+fgnTMw8MTHx+PvF4hwo2MjHRxcYETqODGCftXP/afxaRgy+Li4tnZ2eguRGYG//Zr1651dXV9+fIllUodHh6OjIyETwn0zcXFdezYsZiYGOD6+vp6ED9xHEcu1SUlJXEcHxsbU1ZWhiP2HR0dNBqtq6sLhW8QEhJycHCAIBQEAiEzM/N/eUj+I/huC//+/v66urr/5f0+1He7u7vNzMywP+JcIkoNDQ3V09P7/fffGVe+4NfjxIkTX5JSm5qajh8/jmEYOzu7kZERjMOp46SlpQU4cfPmzeB2r6ysDHlTlpGRCQwMhA/U2tpaW1s7MTHR29uLtJPISTZIqYwoKSmBhfaCBQvu3LkzNDQUERGRkZGBzr9DZUJDQ6WkpKqqqpCzOxkZmYKCgv7+fgcHh69Tak9Pz6lTp2CXCdz9YRgmLy//7t27wcFBIyMjLy+voaGhV69egVN6Nja2s2fPTnLtAYBI95M+CoVCuXTpEmQrICAAWgU6A/A/dsPg/2+n1Pb2dlVV1TVr1qC4IFevXkWaXBqNlpOTw6gFkpKSCgoKYjxuf/HiRfBThWHYnDlzDAwMkpOTGQ9D+/r6grJi7dq1JSUld+7cmTdvHmPoKhqN9vTpU+Qidvr06fLy8oGBgcg1LZNV/058Z13q98rtp0ZPT89nKTUoKMjY2Dg7O/vOnTvIFamJiQmZTDYxMfnSGq2lpQWkVKDUSZ4HEJqbmydRKoVCuX37NgcHBxQ0bdq0PXv2PHz48LPODRClGhsbT7pVWloKlMrOzm5oaOjr67tu3bqpTvhDQ0MlJSVHRkYyMzMRiWhpaeXl5V2/fv3ixYtIcpxKqX19feC3tKSk5O7duxC1G8OwgwcPVlRUmJmZ+fn5jY6OhoaGgrtrTk7Oz7oKRWA0jYI21NbWRpT6p5Hiv5FSaTRaenr6mjVrHj16pKamBrEn9u7dyxi4gUql3rhxQ0hICMVc4OTkNDAwQNHMwLMfRNkCcHFx3bhxA32m+/fvg/drPj4+VVVVSIncPALGxsZiYmLWrFkDdYDPDcoE5n7R3wymEdX3x1co9dSpU2/fviWRSN7e3qAgY2NjCwkJ0dfX19TU/Gxu/zal4jg+MDDg6OjIxcUFq2kMw3h4eC5evMjocAjwLZTKwsIyf/58fn5+Hh4ef3//SQ6QQkNDN2zYAEaUISEh4Jx09uzZR44csbCwuHTpEpLdplIqkUi8dOmSiopKZWXl2NiYjY0NqCZ5eHjU1NQ0NDRSUlLodPr9+/eBbbm4uBgplUKhEInEgYGBjx8/fvz4sbm5uaioiJHxm5uboQ2/L6USCIRz586pqKgQCITY2FjYHOPi4rp58yZjMtgn3L9/P4pvyMrKunXrVmTKNjg4ePPmzeXLl0PMKAzDODg4bty4AdoVJycn+HwrVqzw9/c/fvz4jBkzGPXIMHmMj4/n5ORoaGggdp4+ffq2bdsmRfRj4j8NJqV+f3ydUiEye1dXl6qqKsgUq1at4ubm/tJOyGcpddKiFcfxxsbGqZSK4/jQ0FBaWtqJEyfQztjcuXMdHR0nWW5+C6Xy8PDY2dklJSVt3LhRV1d30royJCRkw4YN4OaOTCZbWVmh+KZLly5lZMDPUqq1tbWqqiqMfwKBgGI9sbGxLVq0COQ+FOeKk5PT2toabeuD61UREZHVq1evXr163bp1lpaWjMG0J0mpMKMwirGTFlifpVT6H35U0QeFXXUTE5OUlJSkpCTkg/nQoUOwtAfDe/DX19TU5OfnB8ZPMNmANgOyGh4erqqqsrOzQ+6ZBQUFS0pKcBxHAcTExMQGBwcrKioEBQVB0QxV+vjxY0VFRX9/P51O7+7u9vf3l5GRga41Z84cRpMyJv4GMCn1++PrlIoc+FdWVjIGnkPb35PwJUoFtXVNTc2LFy9wHC8vL4fRiCi1uro6Pz8fMiEQCI8fP/7tt99A3tmzZw8KGQT4Fkrl4+MLDg6emJi4fv36kSNHYIe6sLAQeBAoFSlYm5qaULBSCOT3FUrt7+8/ffq0oqIiEqmKiop27NgByWbOnAmWqtXV1QoKCsCzRkZGKMPu7u6oqChGRquoqECaVhqNRiaTfXx8YOnNx8dXUFDwdSXVV6RUbW1tCEjV2dl58eLFxYsXHz58WE9P7+TJk9LS0mB0sXTpUjDnADMDHx8fMMgfHR199+6dnZ3d7NmzWVhYDh8+nJiYaG9vjxxdf/z4MSkpCTksh9W9l5cX/BQXF4dkt2/fhnA74MK5trb2/PnzMTEx8MpkMrmmpgZ6IDs7u6mp6SQVDRP/UTAp9XsCBuqk7Sm0yg4KCjp58iSiVBzHExMT0VYV2mqfhObmZsbtKcaFf19fn6enJywzi4uLQSrcvHkzSDdPnz41MzMDoRhQUVEBgTFkZWUZJVkcx69fv85oRIUzCG6IUnl5eX18fGg0WkVFBew4V1VVmZqagsQUEhIiKiqKPL3jOJ6Tk4MCoDIKlYhSz5w5g15EV1f3wIEDSAs5Pj7+/PlzMDCaNWsWMAiNRrt69Sps5mzfvp3RP3RbWxvYyXJxcTk6OjJ+EZh7ysvLwfZ25syZly5dmqQ/GR8fLywsTEtLA4EOUerp06cZk5WXl8+fP//atWvwdoqKik5OTjk5OdnZ2VlZWc+ePYNIENOnTz969CiO40QiEQIHMIaieffu3YYNG2bNmnXx4sWIiAgRERELCwtG1kOBsyDmblBQEHzZ9evXI2rGcXxoaEhTU9PU1PTDhw/bt29XVlZmDJWYlpY2f/58Dg6Omzdv/ux+8n8uMCn1uwGN3oGBAQsLCxhaurq6KDBkRESEsbExsAYirJCQEFjMmpqafjbbjo4OHR0dYBYLCwvGW0lJSbt27YJQwPn5+aCqk5OTAyuC1NTUTZs2mZmZMZph3Lp1C8OwHTt2MA4/HMft7OxAM4CKQE9VVlaC3DRJS9jd3W1sbKyurg6xsuPi4tatWzeJqqKjo4WFhadPn3758mU0sBFhmZubwxUymXzmzBlVVVWQfFHRjx8/XrJkCYpzheP4+/fvDx06BMzo5OSE9Ll1dXUgwLKwsJibm08lERKJFBISAuGeFi9enJCQgFiso6PD2dn58OHDyCBs9+7dUEMVFRU45FpfX19YWLh//34+Pr4nT55QKBQTExM5OTnGM7I4jiPTV35+/rS0tJGREfh2mpqaMM/hOF5aWrp48eKFCxeWlJRkZWUJCAjMnz//6tWr8EUGBwfPnz8PRUOMwhs3bsAqno+PLyIiora2trW1NTY2VktLa9myZTdv3mxqapKRkYH9qMLCQjDSsra2ZmVlVVJSmhSrkYn/NJiU+t0Ams3R0dHy8nIUzvrXX38tKCggk8l9fX1mZmYSEhLh4eGw7QAgk8mXL19mYWHR09ObmidoQsHSHsOwjRs3RkZGQsCSe/fuSUlJCQgIBAQENDU1ocHMw8Pj5eXV398PwfJmz55tb2+fk5PT1NSUmpoqJye3YMECT09PxiIqKipAHsQwbNOmTcnJyW1tbUD6zc3NHh4eKByWuLi4k5PT9evXHR0dIVqcjo5OfX19eXn5sWPHWFlZ3dzcioqKyGQysl5yc3Pj5+c3NzeHoDJhYWHI2mHDhg2xsbF5eXn37t1buXIlLy/vlStXoGh0aMLOzo6LiysxMREt88vLyw0NDWH7S0dHJyAg4N69e7q6utzc3Ozs7Nu3b4+Ojv6sMR+RSPTz8ztw4AA7O/uqVat0dXUvX7586dIlfX39w4cPX716lUQitbS0ODg4LFmyZMGCBYsWLdqyZYuVldW5c+f09fW3bds2b948BQWF0tLSu3fvcnFxiYuL3759OysrC2Tb3NxcAwODZcuW8fHx8fPza2pqpqen29rarl+/fs2aNbq6uvb29ra2tqqqqtLS0rdu3aJQKNXV1QcPHhQVFd2/f7+hoeH58+f19PS2b9+ur69fWVk5ODiYmZl58OBBXl5ePj4+QUHBQ4cOnTt3ztLSUl5eno2NDWyQGxoaNDQ0JCQkduzYcebMGWtr63PnzsnJyaEQZExTnL8TTEr9zmhoaPD19VVXVxcXF5eQkNiwYcO5c+eKiopyc3OPHj26ceNGW1vb4uJidGARHjl69Cjj+SKE+vp6OKQvJiYmJiYmKSmpqakJJ9P37t0rLCysq6ubk5OTmJioo6MjISEhJia2fv16fX39kpKSzMzMU6dO7d+/f+/evWfOnLGxsTl06JCkpKSrqysSnOl0OmybbN++HYrYuHHjqVOnwF6dRqM9e/bs5MmTGzdulJOT27dvn7S0tKCgoKCg4Nq1a2VkZGRlZX18fBoaGvz8/Hbv3q2kpKSlpRUUFAS7LsBrzc3Nnp6ekZGREP/Kysrq8OHDKioqKioq6urqTk5ODx8+tLW1VVJSOnjwoImJCahNESe2tLRYWVmlp6cDbdH+CHwdHh6upKS0c+fOffv2bdmyZdOmTUpKSjY2Nrm5uV9XHTY0NDg5OSkqKu7evRsiG+rr62dmZsLdiooK8Idw8+ZNCAvm7Ox89epVMzMzPT2969evJyQkVFdXu7q6amtru7i4nDt3LiQkBITlBw8e2NnZeXl5eXt737p1y8vL69GjR0VFRQkJCeHh4eCoZceOHRoaGigU9uDgYFpaWlZW1pMnT06fPr1z58799ulUaAAAIABJREFU+/eD8S/+x3FeJycnb29vb29vT09PV1fX69evX79+3c3NzdXV9cmTJzBbP3nyJCsrq7S09M6dO7q6ujo6Ot7e3uBwgP53eaJiAsCk1O+M+vr62NjYhISE/Pz8oqKi58+fOzk5Qfy+7OzsvLy89PT0srKySdFZGhoapga8w3G8vb29oKAgJycHHDXl5eXl/IHc3Nzs7Oyampru7u5Xr17l5OTk5eVBmszMzOrq6paWFtgZq6qqioyMtLa29vX1RbtSiNO7u7vBBRQUkZubm5+fD844aDRaXV0d+Iuqr68nk8ltbW3wFrW1tf39/U1NTSQSiUqlvn37tqamhk6n19XVoe24f9tUeao9A+PFSYnLysrS09NR0G/Gt5ua7Z+W+2/UFv933/TvER6ZBuN/M5iU+t1AZ/C2yejlc2JiAlxbMib79jy/ZTxMTTPpCpVKHRsb+9I2xfcdcjQabXBw8LPu9Zhg4r8eTEr9bmCKA4CxsbHc3FzGM5dMMPG/Ayal/reB/ocz/C85t/9Pg0ajffr0iSmlMvG/CSal/rdhYGCAQCCQSCSm1MwEE38//n9K/eyGwFR8Jc23P/7ZxFOfpX8ZXyl0Uv7fksnUCnwp2V+t86T6fOmpLzXUV5J99l3g/5GRESKRCHvQX6rPV17nG4ueevFLGX7La35Lm0yq/Fdy+9PEf7XQb0/2jYm/Jbe/lPiz3/fr2dKndN1/uwLfUtb3apk/LevbH/n2tvpL+H+U+i1LRTp9cow2xut/qdUm9f4vPT51hDD+89niPjuo/tKI/fpo/JY8v9IU37Fj/Sf66Nf7wJ+W+Kdf56+W+JdKZ8zq62/xHQudmpJOp1dVVbW0tMDP7u7uz8ak+npWdDqdMdrgt7/O4OBgenp6UFBQamoq0mgTCISRkZFJvZdCoRAIhKn5o/+HhoaSkpL8/PzAqG50dLS6unp8fBz8QzY1NTU3Nzc1NdXV1dXW1sKBiJaWFiKROCkAIp1hS/bVq1dhYWH37t1LTk5+//59TU1NRUXF+Pj4wMBAYWFhSkpKUVFRQ0NDc3NzW1tbVVVVeHh4WFhYbGzsmzdvurq6nj9//ujRo9LS0sLCwqqqqpiYmK6uLjqd3tHRkZKS8uDBg8jIyOTk5NbW1qioqNDQ0Li4uPj4+Ojo6ODg4JiYmIqKCuRXgU6nE4nE58+fh4aGxsfHx8fHP3z4MCgoCJmsvHr16t69e5GRkdHR0fX19d/o0+tfKPVbHvg/orOzs7GxcZITo892l48fP46OjsJWNVyh0WiTugWgr6+vpaWlpaUFGhfH8dHRUTKZTKVSOzs7Gc/zEInE3t7e7u5uAoHQ1dXV3d3d3d3d1tbW1tY2KefBwUECgdDR0QFpOjs7m5uboa+gNFQqdWBgoLW1lTGrlpYWZMlPJBLz8vISExPB1nJiYgIMQikUCjhjZ3y2s7OztbW1vb29p6dnYGAAGopAIDDebW1tbWtr6+rq6uzsBHP6urq6srKyrq6unp4eOKcI6O/vh3h5r1+/fvHixeDgYE5OzuPHj+vr65uamnJzc9PS0jIzMzMyMjIyMt69e/f69Ws4qwODub+/Pzk5OS0tLSMjo6CgAEXoA3z48CE1NfXmzZsODg7e3t5Pnz4Fl8kvX75kjFBCp9Pb29ufPn2amJiY9QcSEhISEhJSU1Nzc3ORKyY6nd7S0hIQEBAfH//ixYucnJznz59HR0d7eXm5uLjcv38/PT0d9LMxMTE3btwAM8z4+HgPDw8fH58nT57k5+czutMHEAiE+Ph4Z2dniM3n4uISExMD1pqQMiMjw9HR0d3d/c6dO7dv33Z3d3dwcLh69aqHh0dMTEx9fT2krK2t9fX1dXV1dXBwuHHjho+Pz507d7y8vK5du+bg4ODm5ubr6wuHlMbHx589e3bx4sXTp0+bm5tfunQpODjY2NiY8Vjwt+PNmzf+/v6vXr3C/4xS4Z++vr6EhIRTp06Ji4uvW7dOVVX1999/v3z5squr67lz59CLI7x///7cuXNgVzcpf/BbaGZmtn///uPHj584ccLa2vry5ct3796lUChZWVlXrlzR0dHR0tLS0dE5e/aspaWlubm5jo7OoUOHzMzMJsWLRKwdGxuroKCgoqJiZGSkqamprKysqqrq7u4+ODgYFhYmIyMjLS1ta2trY2OjpaWlq6urpaV15MiRLVu2/PLLL3v27ElMTIyKilJTU9u9e/f27dvV1dXPnDkDU1dtbe3169dlZGRWrVplaWnZ1NTk5eW1a9cuYWHhlStXSktLq6urHzp0SEFBwdzcPC0tDSY5IpEYGBgI1tYQBtHBwaGnpwdq++rVKz09vWXLlhkZGdXU1PxlSqXT6RBKMzY2NiQkJCwsLDExEQ7qREVFhYSEPHjw4PHjx69fv4YglHD30aNHycnJ8fHxDx48SEpKgklsajFdXV3Z2dkeHh729vZ2dnbOzs4xMTFNf7gKBs/kz58/T0hISEpKSk5ODgkJiYqKIhAIZDL5xYsXQUFBcXFx3t7ecPYRPVVcXOzn53fp0iVra2sHBwdra+t79+4lJSV5enq+fv2aQqEEBwe7ubnFxcUlJyc/ePDA29v70aNHSUlJdnZ2ZmZmFhYWFhYW1tbWjx49muTw7d27d56enpDg3LlzZmZmvr6+NTU1jG83Pj7+6tUrsPeGlLa2thEREe3t7WQyOTs7287O7syZM7q6uiYmJhAUMyEhgUwmP3z40MTExMbGBnwzw7NWVlZOTk5WVlampqZBQUGFhYUPHz60tra2sLAwNze3sLBwcHBwdHS8cuXKyZMnz549Cx5GIiMjtbS0zM3Nz58/7+rqWl1dDXX78OGDpaXlzp074bxNd3e3vb39xo0bwY5969at6urq165ds7KyOnDggJqa2v79+8+ePQujF8fx1tZWQ0NDWVlZaWlpKysrNBrB+726uvqWLVtWrFghIyOjrKysrKysqamppqZ2/PjxSWb2NTU1Pj4+Wlpa4uLi4uLiUlJSRkZGJiYmW7duFRMTMzIyyszMBBZ++/YtRKnbuHGjuLj43r17jx49KiYm9ssvv7Czs69evbqsrIxCodjb24uIiKxbt05UVBTcDMJIkJaWtrOzg4BXgNzcXGNj40WLFgkLC8vLy8vLywsJCfHw8DC6Wbh7966UlBTyucfNzS0rKwt+CTg5ObW1tV+8eEGn0z08POBYmqysrICAwB+ObjARERFZWVnwVuPj40OhUBITE4WFhZcvX25ra3vhwoXNmzfDwbPHjx9/y2hkBJ1Ot7W1Xbx4sZub258mplKp5eXllpaW8+bN4+HhgTMUHh4e586dExYWxjBMUFCwpqaG8REKheLn5zdnzhxgScZbYLMhKioKJ2WLi4v9/f1FRETmzp3r7u5Op9NramosLCzAFeHs2bPV1dXhDIKhoSF4OGQcp/AuVCr15cuXAgICq1evjoqKqq2tDQsLk5OTmzVrlpWVVU9Pj4GBAT8//4kTJ+Lj4zU0NNC53piYGE9PTzExMQ4OjqCgoMHBQeRNnJ2dPSkpCfrP0NDQu3fvtLS0li5dmpubi+M4iUQ6deoUeISQkZF5+PBhSEgIuDAXEREJDg6Gt+7o6LCwsIBkc+bMSU1NBeESIn67uroKCgpCht+If9meSklJWbVqFRsb24YNG1avXo26Dh8f34YNGwQFBWfOnKmqqvro0SMNDQ3w68PCwrJ169YDBw4ICQnNmTNn//79QUFBcPAZpiYymVxQUGBqarps2TIREZGzZ8/a2tpKS0tzcHBA1Lnx8XE6nV5eXn727NlZs2ZBiWvWrPH19SUQCKOjoxEREeCdXkREJCMjA6ra29sbGhr666+/cnJy7tu3z8LCwsbGRldXd8eOHfz8/JycnA8ePKBQKIGBgZs3bwbnm5ycnCdPnoyNjU1NTTU1NUW+meXl5XNzcxkPieI4Xltba29vD6ceMQxbunRpYGAghEdHaWg0Wm1t7eXLl5FXdjU1tdTU1JGRkby8vFWrVgkJCQUGBubk5Fy+fBmGoqWlZU9Pj5qa2uLFi01MTC5dugQH/DEMExUVtbOz09bW5uXlVVVVraqqysvLQ77gREVFraysbGxsLl68KCEhwcLCEhISguN4cXExOFUBHDt2DISOjx8/Pnr0SEZGho+PLyEhYWxsrLy8HIVUWrZsmYeHR319/cuXL8+cOYPcdGpoaMBSkUql5uXlKSkpycvLx8XFwaqCSCRevXqVhYVl9uzZZmZmT58+HRsbI5FId+/ehXpKSEh8dqM/NDQU8p81a1ZBQUFdXd3p06fBadOvv/6ak5ODRCR0uH7//v2FhYXFxcVZWVm6urrTpk1LSkqCNOnp6TBuwfNIVFTU/8fel8dTtb3/n0SEIpkaqHQptwxF6lakeUalQZlCStwGkqE5U8qQZFbGVEqSKJHIlCTzcMzDcTjHdBwHZ96/P57X3b/zPdS993PHbuf9F/usvfbaa6/1Xs96nmc9D3pg98SJE1QqlcFg5Ofnw7fT0tJCCTQ9PX3u3LkYDEZbW7uiogI+JR6PNzc3x2AwAgICJ06cGBsb6+7uNjU1hT7R19evqam5dOnS7Nmzw8PDGQyGv78/hOxatmxZfn4+nU4PDAycOXPmlStXsrOzIWxKYGAgPLG1tRXO+D979gz5qqQ5Hh0dHRDnxdLSEk0n9SVUV1fDHBEUFPT29ubcmX369GnlypWLFy/mDN2CIEhDQ4Ourq6AgICBgQFX/NzOzk7o840bN6Kqg3fv3m3atOnMmTPw7/PnzyEcuKKiIiwYdDqdSqXGx8eLiYm9e/eOq4UDAwP29vZCQkIHDhxA40uUlZVBON3Ozs5z5875+vpC4G0PDw/4oCoqKjCisrKyLCwsII5MbGws/CotLQ3iMNqxfn5+P/30E/zNYrFcXV1hvdy5cycst+Xl5RoaGhgMZunSpa9fv4bKa2pqduzYAWxmYGCAamzev3+/e/fuq1evfr3zufB/KDUqKkpeXt7c3HxkZKSyshKNsHn79u2RkZEPHz5oaGgsX76cwWBgsVjggsWLF6empo6NjX348EFXVxeDwUybNi0mJgZWAAaDkZycvGTJksmTJy9atKi8vJxGo9Hp9PLy8u3bt/Px8ampqb18+RLUDqOjo2hmSltbW1SLRKPRnjx5Ii8vHxYWBtOgu7v73LlzkydPFhAQuHr1and3N51Op9PpQBzr1q0TExO7f/8+nU5nMpn+/v5wqHz16tVYLBb88KlUKjoPbW1t0bNMaFfAnnr//v0YDGbKlCnHjx8fGhri0g/Cv/X19WiMy5iYGHAhOn/+PAaDQZPlMRiMyMhIiIpPIBBcXFzc3d2Hh4fpdDoayc3GxoZOp3d3d3t5eZmYmLS3t7NYLFiupaSk/Pz86HQ6JH1qampatGgRpIFis9lPnz7FcOD06dMwQ1gslpeXF2fAvevXr0NMIx0dHRBIGQzGo0eP0CP8wEqwIg4NDQUFBd24cQNGGIVCcXNzg8XpwIEDnKoAFouVm5sLgUq5VDqAFy9eQOUiIiIgR2OxWIh+MmnSpMOHD6Oy/+bNm6GktbU1giB0On1gYKCnp2fFihXASgiC5Ofno4IkfOWbN29C3Ps1a9aAUg8GEh8f34MHD9BmEInEc+fOQf0nT56EXurq6jp69CiQ0fHjx0F58vr1a8jXoqio6OfnFxUVdeHCBeA1b29vCNmlra0Nkfl7enqsra3Dw8OdnZ0lJCT4+fkvXbqEklpDQ4OGhgba+LGxMQKBMDAw8Ku7yMjISJhiysrKaOLVCdHf33/x4kUQcbZs2cIljbLZ7JSUFBUVFTRuC1x8/vw5us4VFBRw6v2qq6thLs+ePTsxMREdPwEBAZaWlvB3cnIyrE9KSkoZGRk0Gi07O7uhoaGtrW3Dhg1cUiqCIDgcDpJLiouLBwUFoePnzZs3np6ePT09SUlJoHpC/i+lok9/8eIFhByKiYmBX2VkZDo6OjifwkmpTCaTk1LhdCKFQvHw8ADRzcjICN3WPHnyBNZ4fn5+SEJDp9OvXr26e/fu8QqTr+P/UOr9+/etra2hO9rb22E1xmAw6Be9ffs2tJhMJkMmZFVVVViRmEwmGtjRwMAANvWfPn0C+hcVFb148SLn6Z3Y2FiQNdatW4euWmiuJHt7e7Qkm81OT08/dOgQPIjFYsXFxUHb1q5d28KRaAjw+vVrdXV1NJNHSEgIUMa+ffs4i8GgwWAw6MLLJUS0t7ejefROnTqF2tA5G4YgSGtrK8wxDAYDYe7KyspA2lq1ahVEpYP+MTc3t7Gx6enpCQ0NRUUnNCooGi+1o6PDy8sLpANjY2MYOkFBQfCsJ0+e9PX1HTp0KDo6Gso/f/588uTJaO6jmTNnRkZGQtsiIyNVVVVRydHDwwP6bf369WgYvYKCghUrVsjKykINs2bNggh+sI1NSEiAPMaxsbEQUX/OnDlo4iN0jWGz2R4eHpqampwB91CglCoqKopOeEgii8FgtLS00I0nUOqkSZMgIFZBQcGVK1cIBEJMTAyq08jNzQVBQ1xc/OHDhwhHelcdHZ2SkpLY2FjYNygrK6OqDEBqaiqsCrNmzYJNfUdHB4S7FhQUtLa2hvaXlJTAijt//vz79++Pjo6iFOnl5QXPWrt2bUlJCVwcGhoaGRnx9PQEZpeUlHRwcOjs7ASxICUlBSJsjY2NPXr0aO/evefPn0dFoQkxPDy8e/duCG7Lx8d3/vz5r5g63r9/D+Q7efJkLy8vztjb8HWGhoaePHnCKYq2trZC2l3obQcHB07FV0tLC6RcxWAwCxYscHd3b21tZTKZvb29oF9mMBjPnj0DSlVUVMzIyCgvL3d0dHzz5g2Dwejr60Pj5qAgEol2dnYg+0+bNu3QoUMlJSVgf6NQKEwmk3Mxdnd3RykVteyhx//QTY+UlBRXpltfX99Vq1bB31yUCgOPSqXGxsaCDKSqqormXkRTcALV4nC4V69eHTlyBPaCvwv/h1L7+/t7enpg/WxoaIDxgcFgHj9+DAWam5szMjJYLFZhYSF8RRUVlczMTPg1KSkJym/evBno38fHBzpRQUGBS51UX18PcoqsrCxaPyqycUaxYzKZL1++NDc3h1jLVVVVkDBOVFT06tWr4xOHEAiEkJCQ7OxsoJKgoCDgggMHDnAWQ+kbDTHHhdbWVhhYQkJCtra2E5IF9AlKqQkJCQiC1NTUwII8ZcoUHR2dR48egexDIBA6OztB8kJpDmV2zuB+fX19MHqA0/n5+R0cHOh0ekJCgo2NDVix0LBy0dHRy5cvRzOAApVA1vj79+9zrvNonGldXV002HN3d/fGjRsDAwMh3ijc/vjx49HR0ZcvXz58+BAo9eeff0ZHOdeBekB1dTWkRB3/U0pKCtw7bdo0GNltbW2wA5CQkLh06RIqsgGlioiI3L59m0QiXb9+3dLSsre3d3R0FJVkc3NzQc8we/ZskCDOnTsHw8zExKSystLS0hIet2HDBi6R7dOnTxCKFIPBXL9+nUKh9PT0cFIqfKng4GAY3uvXr+eKvYBKqWvXruXi64qKCnQAi4iIqKurX7x4sb29HTV/FxcXQ8LtBQsWpKamjhdUoRiVSk1ISNDR0VFWVoY5uGrVKjSaOBdoNNqdO3fgoUJCQoWFhROqFyCBDboE3rt3b9GiRaamprDAyMvLQ6JyIG46nf7o0SM0jZWYmNjSpUtdXFxQeQ0oFXRZcnJyly9ftrKygq30hI1EEITJZObm5qJDdPLkyT/88IOdnd2EoS1QSl26dOl4pQdKqdLS0r+XUtlsdnNzMywGU6ZMiYyMRHu+tLQUrgsLC/v7+5uamtrb238pL9FX8EVXf05KdXZ2hqSSqKNVU1PTvHnzgOlBd9vb24vSvKurK0z448ePw5WVK1dyWY3b2tpABJsyZcqxY8dgwoAqatq0ab6+vmhJoFRTU1N40MOHD2H3KikpGRMTM955gMFgkEgkMpkMowelVD09PShQXl6Ox+PR0f+nU+ro6GhERASavm3BggU7d+7kSjqPYkJKRYFmTNq5c+fTp0/Xr1/PqYoC3Lt3T0NDY3Bw8MWLF6gGHAJlZmdnW1hYoF00IaW2tLSoqKhkZWV9+PBBVVUVbt+0aVN1dXVaWtqjR4/6+vq6urr09PTgpxUrVnypK750Ygql1KlTpz548KC2ttbJyQkkBSMjI07pCSiVn59/7dq1+/fvnz9/vrW1NafYhXBQqrS0dExMjKurKyj1li1blpeXV1dXt2HDBvQtuCi1rKwMpVR7e/uhoSECgQCUysfHt2LFiitXrjg7Oy9ZsmTSpElaWlovXrzgWiS+QqksFuvFixeglACIi4tra2unpaUBVaELibi4eEZGxnjugyv9/f2mpqaOjo5gPYMZAXGvx6O/vx+0TNC9qCz/FbS0tJibmx86dOjDhw8qKipw782bNzmPhwwODnp4eEhLS6PvIiYmZmVlBRTGZDJRShUXF4dU6vLy8qh0NeF70en01NRUVOEGDd61a9f41QKl1CVLlnyJUvn5+Xft2gW8hOJLlLpjxw60ZwYGBoC7MBjMnTt30HtJJJKNjQ3oBObOnWtmZgZbzN/rqvibKNXX15dCoXBWTSKRIMmtrKysnZ1dUFCQlZUVhIm0traur69ns9nt7e0QQx6Dwaxbt46r/ubmZnRzoaenB9MeaE5QUJAzMDuTyUxNTYXc5QhH3ggpKakHDx786sFHlFLnz5/v6Ojo5uZ28uRJR0dH1PT0JUptamo6cODAeEplcwD5v5SKau76+vpcXFzQDsRgMD/++OONGzdQZT/amb+RUhcsWAAhlg0NDcHJA60kNjZWTk4uPz+fxWL5+fmBBnzq1Kmurq7JyckXL15EuwilVB0dHdStJzc3d+7cuampqQiC3L9/X1FREW43MTHx9fV99OjR4OBgXV0dquXU0tJCWWZ4eLihoaGysrK2tra+vr6urq68vJxIJHLtUlFKxWAwurq6W7ZskZSUnDx58tGjR7koD934a2trb9++nZ+f/9ixY+ikgvdFKVVISGjPnj12dnYWFhYXLlyAAH0VFRWwMGMwmL1793IJ1JxSqoODAxelSkpKSktLw6SaM2dOeHj4+O32lygV/aBpaWlWVlagFkM//evXr2HAlJWVRUdHJyUlcXEBChqNlpmZuX37dvBIA+sWkMKEt5DJ5IsXL0IZISEhLnpi/1/AxUePHhkbGwNfODs7CwkJQSMhXwtabHR0NDU11cLCAuJ2YzAYYWHh48eP9/T0sFisxMREWMnmzp3r6enp4OCgpaUFrzm+kZwXi4uLfXx8UIEGXo0rTjZQ6qRJk/T09FA5EX2FqKgoDAYjICBgbW0NXolo/b6+vlpaWvAvg8FwcXEBSt27dy8qzzY1NYE0KioqGh8fj1YOPgmoXQEcLbjMJ78FX6RULBaLMgJIWJxV9/X1LVy4EIPByMjIaGlpKSsrg1C2c+dOtOm1tbXoPNTW1uYanRAkFIPBTJkyxczMDKRUtKM5EzEBpW7cuDElJQVBkICAACgjKSn54MEDdD9YVFQUGhqalJT07NmzxMTEBw8egDcomsRYTU0tMDAwKirqwYMHMTExqEA3nlLhTclkMprAB6VUrtEJLwI8xc/Pn5iYiF6nUCiRkZEGBgboHJaQkLh58yaXTva3UKqIiIixsfGdO3fWrVt3+PBhLik1Li5ORkYG9JsEAsHJyQnmwNy5c7dt28aZocTd3R2+6Z49e1Dd2Zs3b+bOnQt9SyaTPTw8wBdCQEBAQ0MjLCyMQqHgcDhUSl25ciX6Kfv6+m7cuLF169Zdu3bt2rXLwMDA3d29rq7uS5S6fPlyT09PGDmCgoKXL1/m7HDkF0rl4+O7cOFCUVHR3r17LSwsuPY3OTk5QKkiIiIXL16sqakBZzv4FYvFohoMS0tLLgfJ8vJyYBCYMzQarbu7Gyh1ypQpGzduPH36NOiUZWRkQkNDx3+Rr1BqbW1tQ0MDjUbr7OxMSkoyNTVF3bP279/P6eD1FfT29lpaWiooKHh4eMTHx6Myr5yc3MOHD8dPbxaL9eDBA9ikT5ky5cGDB5xiNXucvzmZTLa1tZWXl7e0tLS0tERdSjAYjJ+fH5Rpb29PSUkB43t7e3tcXNyBAwfgXRQUFAoKCmCfCrv4RYsWFRUVtbS0nD17NiUlBRzJy8vLuRaA3t7elJQU9HPk5eVduHABcq+Ji4s/f/6cs50opW7bto1z6w2vf//+fZRSYWyg3XLr1i1dXd3xlHrq1CnQ17NYrKysLJggq1atAnUHWgOJREIlrbCwMOT3i6jIVyi1vr4eHRCcTAFAKVVZWdnLywsM05MmTVq/fj0qiJHJZLClYiaSUtGNv4iIyNmzZ6Hp6KaAS5eamppqYGAAUmp8fDzM+ZkzZ6LRfxEEycnJMTc3V1VVVVJSAm8tEMRCQ0OBUo2MjDgbgNqFvkSpFAoF8p1wUSq6iQPrBJqaVEZGBnRJXV1dHz9+hI+NxWI9PT11dXVhJmtqaqJfEfBbKFVWVhZSyD18+NDIyAhsHVgsFnRbcXFxsrKyz549g4YRiUTUrUpAQODixYuozg6lVENDQxjx4DAwe/ZsVNMNHqnoNPPx8RkZGRkbG0MvLlu2DBWTqVTq48eP0c2jpKRkYmIikUjkGogopRoZGVEolKioKGClxYsXo6ZwALoGu7q6Igjy+vVrJycnkEQeP34MFIZS6qxZs7iEXARByGSyt7c3VKKrq8uVtTAnJwdd4eDR4DAEX/nMmTMEAsHW1hYEVQ0Njbdv33LV/xVKvXPnztWrV9EDAkQi0d3dHUQ5dXV1UFvR6fTOzk40BPh4FBYWqqqqHjlyBM4UnDt3DtIUCggI7N27d0KVy+fPn4Hd+Pj4LCwsxmcUZzKZWCwWuCk9PX3z5s3r16/fv38/JPTW1NSEPtmioQEMAAAgAElEQVSxYwdIIQUFBXv37n38+DFKcy0tLZaWlpMnT164cCHoMTo6OoAQlZSUIHNMaWkp9HZOTs6ZM2e4TjdgsVhDQ0M/Pz/U3MRms0NCQmbOnCklJfXs2TNOzTJq8VdWVubc+MO4go0/Hx/fpk2bQCmETlhnZ2cTE5PxlOrg4IC6Dzk7O4MG2cnJiWu1JhKJqE5gwgX1t+CLlNrc3AxbewyHxR9tfV9fH2rxLysr+/jxI3xUERGRc+fOgUEDQZCQkBCgP01NTa4vXV5eDs4AoBKFi6jJ6Ny5c5xPfPPmjYmJCWhqysvLYQssLCzs5OQEXwhalZaWBiK9hIQEqrtEN/779+/nbMCvmqdQOZqLUhEEGRkZ8ff3d3FxQRCkpaUFKFVWVjY9PR2acfToUTSREYIgFRUVenp6/Pz8P/zww9OnTzmf8nVKhVVHVlY2ODgYQZC2trbQ0NDBwUESiXTt2jUw66GUioonWVlZqFaak1I9PT2BDtatWwcjHhZteXl52PjDFKqrq4NW8fPzo3MgMTER9kQLFy4EOyGKa9euwSusWLECrnAd93z58iUUUFVVbW1tpVKplpaWYFBas2YN6nuAIAhYbzC/ZBWkUqmQdrC0tHTRokV3795FECQ/P19TU/NLlIogyIcPH2BwCgsLo47M8NXc3NxgO7Vx40a4t7u7G2zfgoKCJ0+epNFoLS0t6HK7c+dOLpcSPz8/kHF0dHS4PD2vXbu2fPly0KejAO3W/v37W1paqFRqWlqajY2Nh4cHehKUE8PDw66urlu2bOHciMTHx8OolpOTG++chCAIkUh0dXUFmpCSkoJBiKK3tzckJOTChQsg69jY2Ozbt49zMhYUFEB3CQkJgQ2jpqZm69at+/btQ5cHBEGePXuGwWCWLFkCb52Wlga61AULFnAO9ZqamoMHDx48eBDYGUVHR8e+ffs0NTU5VROFhYXg/A/Z0lB4eXlB/6urq6MX0d3hmzdvYKHi/L50Oj06OlpfXx+1OCEIcunSJVgdd+7cWVVVhcfjk5KSgA3Wrl0LWWS4+gr1E4fB9j9gAkqFduPxeFRm5NQ4wK/Dw8MgpaqpqcEEi4uLA6vRlClT/Pz8YHrX1taCPn7GjBk3b97kXIgiIyNlZGQwGMz27dthi8Fms1HVIWfqYyaTGRkZaWZmhnbBo0ePgBrU1dU591O5ubnq6uowsFBNOZr83dDQkPM1US5DHba4hnhnZycw2tSpU1FHK0BaWpq+vj5oW/B4PKpsArpMS0vT0dFxdHTkPD4QHh4uICCwfv16rg0gaktBBXNOxQI0YObMmTdu3EBvIZPJfn5+27ZtAznryZMns2bN4ppIKSkp8+bNExISunjxIipreHh4gFFo48aNqKUVj8cvWrQIKBXFhw8ffvzxR8wvVgsEQUZHR728vMTExISEhJycnDjDoTo6OsIrLF++HPQwXOqRxMREKCAoKAgTMjc396effgLWNjY2Rk3JaG+YmJgMDQ2RyWQ8Hv/58+f9+/dra2vn5+cjCJKeng4KX2Fh4Tt37oy3yQ4PD4eGhoJpxc7OrrGxkUwmDw8PZ2RkwMKvqKgIOwwGg1FVVQWeJxgM5vDhw8A10dHRwBcCAgI2NjZtbW3wXmQy2dHREWQ6VVXV9PR0TtPZ9evXMRjM1q1bP3/+TCQSyWRyZWXl1q1bRUVFQ0JCYETBIi0mJvbw4UN0OkBfDQ4ORkREyMnJGRgYYLFYNCVMbm4uLP+TJk06cuQI+FZzjdWqqiozMzMgiz179qSnp1dXV0NCcmdn52XLlkG6wMzMzHnz5m3evLmtrQ3VsNfV1aGimba2dnl5+YcPH1atWjV16lR7e/uioiIsFltZWWlrawuukCCienl5gYaEj4/P3t4+Nzc3Ozs7JiYG5vvVq1e5jIodHR3btm0D5XhWVhacgYbjbU5OTtAYNpvd09NTXFwMLj0YDEZGRiYjI6OrqwteGd66u7v74sWLsN9SV1d/+PBhZmbmvXv3jIyMfv75ZxiZNBqtpKTEyspKUlJSSEgIztFcu3ZNV1dXQUFhy5YtqAMcYGxsDIvFPnr0CNJHwpYFi8UODAz8UV0q+5fQ9OXl5ej5ovPnz/f29oKTPGRFr6urA5nlhx9+SE5OZjAYeDwetfhLSUm9fPkSxnpKSsqiRYsmT568ZMmSd+/eDQ4ODg8Pd3R0GBgYTJo0aeXKlZxLXExMDJyfW7lyZUZGBpFI7O7uzsrKOnjwoK+vLyr8Dg4Ognc3Pz//xYsXGxsbSSQSON+hRrPs7Gwmkzk0NIT6t//0009YLJZMJo+OjnZ1dYEvN8zevr4+Go3G2XdMJrOsrAzkaAwGc+DAgYqKioaGhoaGhry8vN27dyspKcXFxQ0ODubl5aHqOV9f38HBwfT09IULF0pKSnp5ebW2thIIBPB6mzFjhpeXF6f6v7OzE1WWge17dHQU5tLQ0FBjYyPK+8DFjY2NeXl5169fFxcXX7VqVVFRUV9fn7e3t6ioaGBgYG9vLyoestlsX19fOTk5R0dHGI5tbW2oPVBdXf3FixcQ68DHx0dUVNTNza2npwc9XjE2NhYUFDRr1ix3d3d050UgEC5evCgtLS0lJeXi4vLmzZuGhoYPHz7s3r1bUFBQXFzc2NgYVW3DBGAymd3d3a6urpMnT+bn5xcREUlMTCSTySwWKzAwcNq0aXx8fKKiolZWVpCI9KeffuLn5588efLKlSuDgoJCQkJsbW1Xr149depUAwODmpoaIpHo6Og4bdo0qM3CwqKwsJDTRInqwd3d3RcsWCAtLW1mZhYeHn7v3j1TU1MJCQltbe3MzEzo5ObmZk9PTzU1tRkzZkhJSW3ZsuXevXskEolKpTo6OkpKSk6fPl1eXt7V1RWPx7PZbDAczZgxQ1xcXFlZ2cHBAa0KQRB/f38lJaVZs2Zpa2vfuHEjPDzcxsZmwYIFx44dAy9UHA538uRJUVHRRYsWvXz5EigVVSW9efNm6dKlYmJiy5cv9/f3h/UYh8N5eHgoKyuLi4uLi4vPmTPn5s2b46MZwCvfu3dvw4YNUlJS8+bN09PT27t3r4KCgrq6enh4OIVCaW1t3bNnj5ycnLKy8pUrV0CtOTw8fO7cuR9++EFOTm7u3Lnz588/e/YsnHLeunXrTz/9tG3bNlNT0y1btigoKJw7d45KpVIolLCwsPXr18vLy8+dO1dOTm7BggWKioo//PDDwoUL5eXl582b9+jRIy5PCRwOZ2tru2PHDj09PV1dXUNDww0bNixcuNDR0RHVIyEIkpycvH79+nnz5snJycnJycnLy6uqqiYkJHAmM0cQpLu7293dXVNTc+7cuQoKCgsXLty4cWNcXBzK40Qi0dDQcP/+/TY2NseOHTt27Njx48ctLCwcHBwKCgrG6086OjpcXV0NDQ2PHj1qbW1tbW197NixCxcufMl37SuYQEql0Witra3BwcHTp08XEBAQEBAADx4waMDpdWtrazExMQEBAQkJCXt7+7KyMhaLVVpaunz5cpgSWlpawJVjY2MvX77cvXu3sLDwihUrfHx8YmJiDh06JCYmtn79+ry8POh6GFVjY2M+Pj5ycnLg1nfq1ClTU9N169b5+vr29PSwOeJgDQ0NPXjwYM2aNVJSUgYGBn5+fnfv3j106NDMmTNFRUX37NlTX1/f398Pvu6w7MyZM8fc3DwhISEvL+/48eOSkpLCwsLCwsIqKiq+vr6goETR3d3t6en5ww8/CAsLi4iISEpKwpdbuHDh/PnzxcXFd+7c+fbt27i4uF27domKikJVy5cvj42Nffz48fbt2+FUu4GBwbFjxw4dOrR48WIXFxf0k7NYrJKSkmPHjklJScG9CxYssLe3h30uk8lMSkqysLCAFKdTp04VFxeHITt//nxpaWlBQcELFy50dnbeuXNHQUFBVFRUSUkpNDQUljHUFcHFxeXChQvQsdu2bUNfWVxcXFNT08XFxcXFBU4Sz5o1y9XVFT12hSAIHo93dnaOiIiAPQSATCZnZGQcO3Zs48aN0J4FCxZoamoeP348IiKiqakJHfTsX/yBYmJijIyM9u7du2/fvr1791paWr548YJOp/f09Hh5eYFRy8jIyNbW1tbW1sjICIodOHDA3Nzc3Nz88OHDBgYG+vr6MTExWCw2PDz8wIEDaG3GxsZ+fn6c21jOjdS7d+9cXV2PHDliZmZ25MgRW1vbuLi46upqVDx8//79iRMnTp06FRMTExYW5ubmdvnyZTCF9/T0pKSkhISEBAcHJyYm4vF4Op2emZkZERERERERGRl5//79qKgocG6H2j5//gyhaqKiolxdXa2trb29vVNSUkAUgAWmoqIiMDDw6dOnnCpFVN9y9+7d0NDQe/fuvX37Fgq0trY+e/YMnhgeHh4WFpaVlcUlmKN9TqPRent7nz596u/vHxERERwc/Pjx446ODrDM0Ol0HA7X2dn54cOH4uJiaPbo6GhOTk59fX1XVxcOh2tvbycQCB0dHQUFBUQiEYfDZWVlRUdHx8XFffz4ET0KCDF5Ozs7cTgcDodrbW1tampqampqbm5ubW2dMOoVxJrq6+uD6EIvX7589epVe3s7qgwFkMlkCA/U1dXV1dXV2dnZ3NxMIpHGRw4bGRmBqpqamhobGzs6OtCwQWw2m8FgQAQiEolEIpEGBgZ6e3uJRCKJRELr4ayTTqcTCISurq6BgYGhoaGhoaHe3l4CgcDl6fRbMAGlUqnUysrK6Ojom78gICDg6dOnsNKSyeTMzMw7d+54e3vDr0FBQTk5OSMjI3Q6/e3bt5BU0tPT8/379/AtmUxmW1tbcnKyt7d3WFhYdHS0l5fXkydPJjzpNTQ09PbtW39/f3d399u3b9+9ezctLW1C9xE6nd7Y2BgdHe3r6wtiiI+PT3R0dEVFRUdHB5xPTU5Ovn79ekBAwOvXrz99+pSenp6ZmVldXf3u3bvi4uLy8vLy8vKKioq2tjbOME4IghAIhIKCgvz8fChTUlKS/wsKCgo+ffrU2tpKoVDweHxFRUX5LygrK8Pj8f39/a2trRAjKi4u7vbt2xEREbm5uVxGiaGhodra2rKyMvReLBaLCiAEAqG2that+dOnT/D0wsLC4uLisrIy2Dd0dHSUlJSUlZWVlJTgcDhO1Qqbze7r64N9EIvF+vz5c0lJCdRWWlr66dOnxsbGxsZGuL24uLixsZHLI62/v39gYGC89z6BQKirqysqKoLeqKmpIRAIEx5FpdPpeDy+qakJ5l5nZ2dDQwPqZUUmkzs6OmBO1tfXQ4Z6KNne3g6ztLW1FS4ODw9DMDrO2mACf8WRbnBwsK2trbGxsaGhAYfDccX0GRoaamtrIxAINBptdHS0r68Ph8OhhAUbMjg6BZEoQIFApVKpVOro6CioJtAph3bU2NhYV1dXc3NzX1/feDcsmCkT9hVYAiGOGtxIo9EoFMro6CiVSh37BajT/nj/E+SXgG0UCgV2AxN2C1dutPEFOJUSFAplwo/7R8CZje0/hgk2/uAq393dDSMGJWxYedDVBv0VgtGhw3p4eHhoaKi/v59MJsNARCuHwt3d3egWfvzT4Q+Io9zb24ueEfoSmEzmwMAAgUAgEAhEIpFrdsHqhE4SUAX86vhgs9lfSX73u0ClUnt7e39vuEweePg6OHcD/4OjDw9/Hb5onpoQXwncy54o4urXv/f48l+qf8J6vlQ5iwNc5b/UEh54+ObQ2dk53l/qTwHXTOFNnN+Fr+We+hKRIRy6j/Fbjy8x3YSblN/79D+lMA88/AfQ09PzpSNYfxCg9gUt5HjvAh6+Dl46Px544IEbVCq1paUFfGn/6bZ8Y+BRKg888MANBoNBJBKJROKfYlH4rsCjVB544AanHuk73PbydKl/BDxK5YEHbrB/STMxYfpIHnj4CniUygMPE6OysvJ/y2zKw/cMHqX+Y0B9J/7phvAwMcDt+p9uBQ/fGHiU+o8BsiJyZWblgQcevmn8A5T6pYN03xsgpMiXko7wwMMfx3c+xf4R/DOUyvUHDzzw8CcCPQXAm2J/P/4ZSoWQMH//o3ng4XtAZ2cnZ0BbHv5O/DO61Obm5r/oeDIPPHzn4EVU+Wfxj+lS//7n8sDD9wDe5PpnwbP488ADDzz8aeBRKg888MDDnwYepfLAAw88/GngUSoPPPDAw58GHqXywAM3OOOs/9Nt4eEbA49SeeCBG8Ck43Pt8MDDr4JHqTzw8DXwBFUefhd4lPp9YWRkpLOz81fzzn4dkEH2V7MSsdnsjo6O1tZWzlTY48FkMgcHB0kk0vDw8PiSkLKXQqG0traiKen/aoyMjNTV1WVlZdXW1vIolYffBR6lfhcAXhgYGAgNDbW2tn79+vUfqWdkZCQjI+Pz58+jo6NfKTw0NHT9+vULFy6QyeSvFBsdHc3Pzw8JCbl169bbt28hQTeqx6TRaKmpqf7+/mfPnn348GF/fz/y10uO7e3tp0+fxmAwZmZmf+mDePjvgUep3xEyMzM1NDRkZWVjY2P/txqAyzo6Onbt2mVvb9/V1fWVwng83sPDw8fHh0KhfL3O8vLybdu2CQoKbt++vbq6GvlFj8lms9va2pYtWyYkJGRtbd3U1PS/Nfv3YnR09O7du0JCQocPH/57nsjDfwY8Sv0uAFRIJpMvXbqkrq5+//79P1JVamrqtGnTpKSkiouLv1KSwWD09/cPDg6iRh4Wi8VgMDhtPtAwIpF48OBBDAYzZcqU5ORkKIkgCIlE8vb2njRpEgaDefbsGesXoPdOKK6O10gwGAw6nc6VGv1LhZlMJpVK/fjx47Jly4yMjNDyVCqVM7cdGqCSwWAwGAyefoAHAI9Svy+Ehobq6OiEhYV1dnYWFxdD1Pr+/v7i4uLMzMyamhoajTYyMlJaWlpUVESj0cbX0NXVdeLECXl5eQwGExERAdpPIBQKhVJWVkan08vLy5ubm0dGRrBYbHNzM3pjcHDw+fPnPT09sVgswsGJAwMDFhYW0tLSGAzG0tKyra0Nbqmvr1dXVxcQEJg0aVJ2djaCIC9fvvT29m5oaGAwGIWFhZ6enu/fv2exWC0tLffu3cvOzi4vL7e3t/fy8uro6IBKcnJyXFxcTp06FRQUhMPh6HR6bm6up6dnWVlZdna2s7NzQEBAfX09FMZisTdu3HBwcDAyMhITE4ON//DwsK+v786dO21tbZOTk8lkcnd3d2Rk5K1btyIjI48ePXr8+HH0cTx85+BR6veFu3fvqqurr1mzRldXd/HixYaGhoWFhRUVFfr6+kuWLLl16xaTyWxoaDAxMdm7dy8oLrmQkZGhpqYWGxu7fPnyNWvWVFRUwPX8/Py1a9euWLFi48aNysrK+vr6JiYmK1asuH79OoIgLS0tVlZW586ds7Ozk5eXj46ORjhERTKZfOPGje3btysqKs6bN+/Ro0cIgrBYrLS0NC0tLSsrKxkZmRcvXiAIEhwcLCkpefr0aRaLlZWVJS8vb2RkVFxcfOnSpTlz5qiqqurr66uoqMjIyPj5+VEolKioqLVr13p4ePj5+S1fvtzHx6enp8fMzGzGjBlr1qwxNDRUVVWFChEEaW9v3717t42NTUZGhpWVFQaDOXny5NDQkLOz8+LFiwMDA+3t7VVVVTMyMoqKitTV1aWkpDQ0NFRUVNasWVNXV/e3fEAe/u3gUer3haCgoDlz5qxevdrb2xv22vv27ausrHRwcMBgMKdOnUIQpKCgYNmyZUeOHBkf05ZIJLq7u1tYWLBYrMuXLwsJCfn7+4OgWldXZ2JigsFgNDQ0Ll68GBoaeunSpenTp5uamiIIEhMTIyIi4uvr29bWZmJiEh8fj/yyu0cQZHBw8MKFCwcPHjx27JisrOzhw4dJJFJLS8uJEyfOnj0bExOjoKAACoGEhAQ+Pj5tbW0EQdra2tasWbNmzZr379/Hx8fLyMjMnz///v37YWFhampq5ubmeDz+woUL2tranz9/zs/PnzZtmq6ubl9fn7e3t5CQ0IoVK6Kjo+/fv79w4cK1a9d2d3dfvXpVTEwsJSUFQZCHDx+KiIicOHGCRCJZW1vv378fZFUMBhMcHIzD4YyNjTEYzMGDB1++fJmVlUUikXh7fx4QHqV+b7h7966SkpKXlxeCIK2trevXr585cyYWi8Xj8crKylu3bu3t7X3+/LmOjk5xcfF4l6ZXr16pqKiYm5vHxMRYW1tPmjTpwIEDqJGqsrJSWlr67t278G9HR4e2tvaOHTsGBwdfvHgxd+7ctWvXBgYGxsbGtrS0IAgCBigEQfr6+mxsbAwMDF68eKGnpycuLp6UlJSSkrJq1aqcnJyIiAhZWVlguuTkZAkJiS1btiAIMjw8bGNjs3v37vr6+v7+fm1t7UOHDiEI0t/fv3///hUrVtTV1WGx2NDQ0Js3b1pZWU2dOlVFRYXJZPb19SkpKYFkOjo6un///pUrVyYlJWlra69fvx628G/evJk3b56JiQmbzS4rK7t69eqZM2f27NkjICAQEhKCIEhoaKiUlNTz58/RzuFRKg8Ij1K/N9y5c2fNmjWw7x4bG/P29p45c2ZZWRmCIDY2NlJSUm5ubr6+vkeOHBlPEKOjo+7u7qKionv37rWysjp06NDcuXPl5eUTExOhQG5uroyMTFhYGJ1ORxCkpqZGR0dHVVW1qqqKwWCEh4f/8MMPGAzGwMCgqKgI7ELwlMHBQRcXF0NDw9bW1sjISFFR0fXr15ubm9vY2FAolBs3bkyfPv3ly5cIgiQlJYmJiW3btg1BEAqFYmNjo6+vX1NT09nZuXLlSjDQ43C4rVu3CgsLl5aWNjY2Ojo6WlhYuLq6rly5cvny5Ww2m0AgKCkpHT9+nEwmEwiEPXv2LFu2LCQkZMWKFTt27CAQCAiCFBYWKisrm5mZMRiM7OxsCwsLS0vLc+fOSUlJRUREIAji7+8vKSmZkJDAO2HFAyd4lPp9ISAgYM2aNeBERaVSr127Nnfu3PLycgRBCgoKQLFoZmb26NGj8UxRWlpqbGzs4ODw7t27wsLCvLw8e3v7KVOmmJiYgJtUcXGxrKzs/fv34d76+npdXV0tLa3S0lIcDtfY2Pjq1SsDAwNBQcHjx49zephSKBQPD49Dhw7V19e3trZu3boVg8EoKysXFRVRqVQXFxdhYeG0tDTkFykVKLW7u3v37t0bN27EYrF9fX2rV68GJQMej9+1a9fMmTNramrs7OxgLz86OmpgYKCiotLX11dRUTF//vxTp06Njo4ODAzs27dPR0cnOzt79erVUlJSqampCILk5+fLy8sfPXq0oaFh586dO3bswOFwKSkpMjIy165dQxAkKioKg8G4uLj8fR+Ph28BPEr9vuDr67t48eIbN24MDQ0VFBRs2LBBX18ftbA7ODjw8fFt3bqVM389yJL9/f3nz59ftmwZp+NUUlLS3LlzpaWl79+/39fX9/jxY1FR0cuXLxOJRARBCgsLVVVVlyxZkpiY6O7uvnnz5k+fPlVXVysqKh44cAAy5UDlPT09Fy5c2LRpU0ZGBpPJvHbtmoCAwLFjx1gsVmtrK6hor169OjAwUFRUpKKisnTp0tzc3ODg4KlTp86aNevt27dFRUU//PDDxo0bcThcdXX18uXLp0yZ8vbtW319fQwGc+3ataCgIGFhYVlZ2YyMjLdv38rIyOjp6XV0dNTW1mppaamoqOTl5V28eFFMTGzp0qUpKSm3bt0SFBTcunVrUlLSli1b5OTkLl++fPLkSUFBwTVr1hQVFV28eBGDwZiamvb19fG2/Dyg4FHq94X79+/Pnz9fV1f3zp07R48e1dbWTktLg306giAJCQlLly51dHQcf2NcXJysrOy8efMiIiJQBomOjlZSUhIWFt6xY8edO3f09PRERERUVFTAOn/79m0JCQlpaWkHB4dbt27JyMhs3rz52LFjGhoad+/eRaVgBoORkZGxcuXKhQsXOjk5EQiEnJwcc3PzhIQECoUSHByspaUlISGhpaWVlpY2ODjo7Ow8Y8aMRYsWbd++fenSpT/++KO7u/vx48elpaXnz5/v5eX19OnT2bNnS0pKenh4gLF+wYIFGzduXLp0qYqKSkBAwOnTp+Xl5eXk5FJTU+/duwd2LX9//66uLltb21mzZs2bN09bW1tDQ2Pv3r1JSUk+Pj6zZs3S0NC4du3aypUrtbW1jYyMFi1aJCEhoaGhAcvA3/HxePgWwKPU7wtDQ0MfP368cuWKqanp7du3S0pKOJ1Po6OjjY2Nc3Jyxt9YWFh448YNPz+/1NRUlEHevHkTEBAQEBAQHBwcGxsbHBzs7+8fGBhYXl7OZrOzs7Nv3brl4+OTkZHR3t5+9+5dPz+/4ODgT58+kclkNpsNrEqn0ysqKsLDw1+9evX582cSiUSj0YhEIoVCYTAYPT09TU1NWCy2oaEBQhN0dXWlpqY+ffq0sbGxra2tpaUFj8e3tbXV19djsdiurq6BgYH6+vqGhgY8Ht/b29va2lpTU9PU1NTa2trS0kIkEjs6OhobG+vq6gYGBohEYl1dXUNDA6hQ+/v7sVhsRUVFQ0NDe3s7DocbGhoikUhYLBbUCx0dHW1tbc3NzbW1tQ0NDY2NjTxbPw+c4FHqvxd/3UQlEom1tbWcbqeVlZUFBQXGxsZ2dnZjY2Pjb6FSqcPDw2QyGdgQLpLJ5KGhoZGRkaGhof7+/qGhIQqFQqFQgKbHxsaGh4eHh4ch1gkUQx2zUNsUHEwaGRmB6zxrDw/fNHiU+q8DlUptbGxEKeavBpvNLikp2bFjx6JFi3bt2vX+/fu/57k88PCfBI9S/3Wg0+k4HI5Kpf6l20nObO9YLPbEiRNHjhxJT09H/rB0jMqe4581/tG/pZ4/qx9+43O5Sn6lMHrM/09p3m95Ig//fvAo9d+Lv5pSOUOQdHd3o0FU/xRK5XwEejj0pfEAACAASURBVAX9l+uPCTf7XKT8x3uD65WR38DpfyfBNTU1FRQU8Pj0WwePUr9r/EUTeHBwEA2nwkmpE+Lr+UhIJNLY2NivVvJbwMmPUO2EdTIYDAKBMKFCmQtkMrmurq67u/tP0f9+/vz52bNnCO8U1jcOHqX+GwGhlerq6pqamurr66uqqiorK2tqavB4POrw9D+DTqd3dnZ++PChqqrqT7cFMZnMz58/37p16+7du/X19UCFKEe0t7dnZWWlp6enp6d/+PChoqKisbHxS5Jgd3f3s2fPvL29S0tL//hbI7/we3t7++PHjz08PCAaFhdqa2vDwsI8PT2DgoLS09OrqqogJPaEyMvL2759e0hIyNdDcf8PjfyzauPh7wePUv+NoFKpQUFBBw4c2L59+/79+y0sLMzNzY2MjE6fPl1RUfEHpZiBgYGbN2/OnTv3wIEDqAfVnyIG0mi0rKwsPT297du3y8jIODk5oUcGqFRqbm6unZ2dsrKykpKSkpLS+vXrf/zxxyNHjnyptpSUFFlZWTExsXv37gFnjYyMjIyM/K52chUeGxt78OCBhIQEBoN59eoVZzEWi9XY2Lhp0yYNDY2jR49u2rRp+vTpa9eu/fTp0/iq4O+MjIylS5f6+PhA877UMM4147drEnhK1W8UPEr9N4LNZre2tpqZmU2aNMnQ0PD58+fPnj1zc3PT0tKKi4v7LXvSr4DBYNy9e1dBQeHnn38Ggaijo6OlpeWPp3Wqq6vbvHnzqVOnWlpa7ty5ExYW1tfXB6+Tlpa2dOnSAwcOZGZm4vF4PB4fHx8vJSW1adOmL9VGIBDOnDkjJiYWEhICUmpERASc9P+fwWaz8Xj8/v37J02aBHFYUAwMDLi6us6cOTMzM5NCoRAIBCsrK21tbc7TYkwmkzMKNZPJJBKJw8PDnIxJo9EmpEJOpzG4wmAwxkekpdPpXNGyefi2wKPUfy8uX76MwWAuXLhAo9HodHpzc3NQUFBWVhZQ6oRy5Ve2jZyF09PTf/zxx3379oFP6JUrVwICAvB4/K+aiTjBZDI5Tw2x2ex3797JyMgEBAQwGIyRkRESiQQE1N7efvDgQUlJSU7BkEqlenp6WllZcYljnP8+fvxYWlo6LCyMRqNVVVVpaGi4uLgwmUwuk9d4Uz6nfnZwcLCiogJiX0Gz7927JykpCYpLFB0dHTt27Jg6dSrEukYQ5M2bNzdv3kSjU9Pp9JycnCdPnkCoKjabTSKRGhsb+/v70eeWl5cnJiYWFhZCuq3R0dHq6urh4eGBgYGcnJwPHz6gaoSxsbE3b94kJyfX1taixEokEl+8ePHy5ctPnz79icoEHv5O8Cj13wsPDw8MBuPh4YEgCJVKbW9vhzSiCIKkpqY6OTldvXo1JSWlp6cHykNEent7e09Pz4aGhu7ubn9//+DgYBKJRKVSb9++7eHhAembKioqjhw5Ym9vTyAQTp8+LSEhsXLlylOnTrm6urq6ut64cSM7O5vBYFRXV9+6dSsuLq63t5ezYQQCITg4WEdHR1tb+/z581BncnLy5s2bJ0+erKmpefr06c7OTrR8QkLCtGnT9uzZwxWAdXBwsLm5+cOHD/r6+ocOHYJbLl26tGfPnqKiIgRBcnNzZ82aFRISkpubu2vXLgwGM3PmTFNT03Pnzm3bti02NpZCoTx8+HDbtm12dnZPnjxxc3Pbv3+/nZ2dkZHR5s2bP378GBYWdvDgwc2bN2/YsCEsLAxBEDabnZiYKCsrm5SUxNmYkZGRwMBAQUHBRYsW3bx5c3BwkMFg9PX1wQLW3Nxsbm4OAVZWrVr15s2byspKXV3d9evXZ2RksFissbGxCxcu7Nmz5+DBg9ra2p6enpWVlXp6empqaocPH9bR0Zk/f/7y5csfPHiAIEhfX9/Vq1dNTEyMjY21tLT8/PwQBCkuLjY3Nz969OihQ4c0NDQuX74MYRB4+LbAo9R/L9zd3fn4+KysrEpLS728vJydneH6s2fPtm/f7uPjc+XKlc2bNz98+BBBkJKSkt27d7u6unp7ey9ZsuT06dMfP340MzNTVVXNz88fGxtzd3eXl5eHgPnv3783NDT08PAgkUg3btyYOnWqmpqav79/VFSUtra2iooKpFCtrKxUVla+e/cuZz4+PB5/9uzZvXv3enp6Ojk5KSkpHT58uKqqqqam5uzZs8LCwvr6+omJiejRrKGhoXPnzmEwGBsbmwnPL5SWlioqKvLz80OCAEtLSwkJCQg/WFhYKCsrGxIS0tjYCKf1jxw5AkFY+Pj4jh07Njw8XF5eLi8vP3PmTD8/P2dnZ35+fikpKUtLS0tLywcPHixevPjo0aNPnjxZtmzZxo0bR0dH2Wx2QkKCjIwMJ6WCmNnT03P69GlBQUEREZFdu3bFx8cDn+JwOHt7eyMjo8TERDRaSnNz86FDh6ZNm5aYmEij0dLS0iC6oJ+fn5qampSUlLe3N7Rn06ZNAQEB58+fFxMTs7GxodPpkZGRW7Zsefr0aWpq6qxZsyBatqOjo5ycnK+vr6OjI6ThQuVlHr4h8Cj13wt3d3dxcfH9+/cnJycbGBgoKipWVlZSqVQ3NzcrK6uurq7Y2FgFBYXbt28PDAw4ODioqakVFxcPDAyYm5tbWFgUFBScOHFCUlIyOTmZTqe/ePFCXFwc4kO/fv1aVVXVxMQEQZCenh5FRcXDhw9DXqaLFy9KSUkFBwfTaLRnz57p6OgUFBSgTWKxWElJSbKyssDvDAbj0KFDAgICt2/fRhAkLy9PWlo6KCiI8y26u7utra35+fmtrKzGB7hCftlxi4qKQoxBPz8/DQ0NkCjz8vIgACuCIKWlpRs3boRYpRDM1MLCAjh6/fr1K1as+Pz588uXL5cuXbpr166mpiYCgfDx40c3N7fs7OysrCwlJSV1dfXW1lYWi/Xw4cMJKRVBEAKBEBYWpquri8FgZGVl3d3dh4aGiouLFyxYAF3X29sbHh6elJTEZDKfPn0qKyv7/PlzMplsaGiooKBgZmbm6uq6YcMGNTW1J0+etLa2KigoQF/h8XgNDQ1jY+Pa2trt27cfOXIE9vvPnz9///59VlaWlpbWsmXLkpOT4+PjDx8+vGfPntLS0j9/VPHwF4NHqf9eXL9+XVFR8dq1a01NTQkJCba2tjk5OTQarb6+/vHjx4GBgQcOHJg/f/6NGzeam5v19PQsLS0hql55eXlZWVlzc/PRo0fnzJkDgU4yMzPnzJkDEekzMzOXL19ubGyMIMjY2JiysvKpU6fA1b+qqmrdunU7duyoqak5cuSIv78/ZyiAkZGR69evz5w5MyYmBvSkgYGBfHx8J06cQBAkPz8fGJDT6jIwMHD69Gk+Pr6TJ0+CtMvl/9/Z2amrqztt2rTKykoEQYKDg1evXg00WlRUJCsrGxoaCikC165d6+npiSDI27dvFRUVraysgFJXr15tZGREp9Pz8vI2bdp06dIltLWJiYlOTk52dnaKiopaWlo4HO5LlEqn01HGLy0tdXZ2lpWVlZKSevv2LQjLUVFRXNakxMREGRmZ1NTUgYGBRYsWLV682NvbOzQ0NDw8HELPtLW1zZs378qVK2NjY62trTo6Ort3746Pj1+6dKm5uTmne9azZ8/mzJmzb98+CNrS1NRUWVk5PlEND/9+8Cj134vr16/PnTs3PDwcQRAqlYrD4SCBc2Njo5OTk5mZmb29vYqKioWFRWdnp56e3q5duyCcEoIgJBKpoaHh7Nmzc+bMASt5Tk7OnDlzIiMjEQR59eqVjo7O+fPnEQQZHh5evHjxqVOn0Bnu5+c3Z86cs2fPLl++nCut9MDAwLlz52bMmBEWFgaUev/+fSEhoaNHjyIIkp+fLysrGx4ezkk9dDo9KCho0qRJO3bsAKMNakMbGBgoKSn59OnT4cOHJSQkwBAUGRmpra0dFRUF7YQK6XR6QUGBmprajRs3EAR59+6dkpKSra0tPEJXV3fr1q39/f0QAdbV1RX4+uPHj2pqart27SooKLCxsdHQ0ID+SUpKmjVrFmeOEwRBenp64uPjP378iF5xcnISFRUNCAgoKioSFhY+deoUvDIej3/37t3IyMjz589nz5795s2boaEhFRUVZWXlDx8+wL3t7e2VlZUtLS0LFixwc3MDX+ANGzbo6OgEBgYqKytraWk1NjZC/5eXl4eHhy9atGjt2rVg+2KxWBEREdXV1X9wCPHw94NHqf9eeHt7YzAYkMtQDA8PGxoaLly4sKioqLu7W0tLa9euXc3Nzfr6+rNnz3716hWZTG5oaAgMDMzOzg4LC4Mw9VQq9dGjR1JSUl5eXgwGIzc3V11d/eDBgwiCjIyMKCgoHDt2rLm5GVSHeXl58+fPB4MSHo/nerqfn9/06dNtbGyAH318fGCDjCBIbm7ujBkz/P39uZwEampq1q5dKyIiEhUVhcq8fX19vr6+R48eff/+fWBgoJSUVFZWVldXl6Ojo5KSkr+///Dw8K1bt2bMmBESEkKj0VJTU6Wlpc3MzLq6ugoKCrZs2aKnp1dSUvL58+elS5fOnj379evXr1+/1tTUtLGxAcq+evUqHx+fm5tbVVXVtm3bQLimUql37tyZPn16QkICZyOxWOzu3bvNzMzKysog4Nbly5cXLFgQGxtbV1enoKAgLCwcHR0NsVxtbW37+vqioqKEhYXv3r3b29t7/Phxfn7+w4cPv3nz5vHjxz///HNAQEBhYaGMjIyNjU1fX19paamqqqqqqmpUVNSBAweEhITs7Oxev3597dq1M2fOxMbG2tjY8PHx6evrZ2Rk+Pv7a2tr83Sp3yJ4lPpvBJvN7u3ttbOzw2AwdnZ2nBE5SSSSqqqqsLBwaGioj4/PpEmTNDQ0CgoKbt68CTmQr127dvLkSTs7u/r6+pSUFGlp6fPnz8fHx1tZWfHx8W3atKmhoeH169czZsxQUlLq7e0dGRlZtmyZhoaGj48P2O6JROKZM2fExcVjY2PHO042NDRs2rRJSUkpOjr68+fPe/fu3b1796dPn6hUalRUlJiY2OHDh8vLy7m8XN+9e7ds2TJFRcVLly59/Pixurr6xo0bu3btCg0NZbFYr169kpeXNzExcXNzW7FiBYiEBQUFkB3axcWFRCLl5uaqqKjIysoGBgbm5+dbWFiIi4tv3bp1//79c+bMmT59ur29Pcj1urq6dXV1LBYrODh4zpw5mpqa+/btmz9/voiIiKmpaVNT044dO/j5+a9du8a59e7o6Dh48ODs2bN//vnnyMjIwMBAbW3trVu3gpNTXFzcggULpk+fLiYmNmfOnPj4+OHh4bNnz0pISBgaGtbU1NTX1+/cuVNcXFxcXHz27Nl2dnbt7e33799fsGDBtm3biouLY2JiFBUVlyxZ8vDhw8LCwp9++klKSkpaWnrhwoVRUVEsFgvigUlLS8vIyMjLy9+5c4dT9czDtwIepf4bQafTQ0NDf/zxx+nTp2tqanJuUalUqru7+/z58xcuXLhv3z41NbWVK1d+/PiRSCSeP39+1qxZsrKyO3bsyM7OZjKZWCz24MGDs2bN0tLSsrW1XbRo0ebNm9++fevl5SUuLj5v3rygoKChoaFbt27JycmdOHECzXWalpampKTU2tqKTBRHqri42NTUdOHChQoKCtu3b8/OzgZ1hKOj4759+zZv3mxpacl13JPJZJaUlNjb269cuVJBQUFZWdnY2DgjIwPk4r6+PicnJw0NDTc3t8jIyDNnziQkJOTm5hobG+/ZswcaBskE9fX1k5KSaDRaTk6OoaGhsbHx27dvb9++7eTkdPfu3UuXLu3bt8/c3PzBgwejo6N4PP7mzZsWFhaPHz9+8uSJk5PTs2fPcnJyrKys9uzZc+XKlebmZrSFw8PD2dnZkZGRly5dsra2NjIy8vLyAmpGfnEjPXfu3JkzZ96/f0+lUmtqagICAu7du/f48ePm5mY2m43D4W7evOno6JicnNzV1TU2Nvb+/fuYmJiYmJiampr3799HRkZGRkYWFBQwmcyKioqoqKjg4OC3b98CdbJYrM7OzuTk5IiIiBcvXgwMDPxFo4uHvxQ8Sv03gslk4nC4qqqq6urqmpqa3t5eTm/2wcHB+vr6z58/NzU1NTU1NTQ0gJWmv7+/urq6tLS0qakJpEsajdbV1fX58+fKykocDtfQ0NDc3Ewikbq6usDtqauri8FgkEikqqqq9vZ2OKSEw+G8vb3t7e1hqo8/iAlnkEpLS4uLi5ubm+GukZERCIPf2NiIxWI5/aXQGvr6+mpqaj5+/FhSUtLS0gKqSfYveadra2sJBAKFQunt7YWtd3t7e2dnZ3t7O7zOwMBAZ2cnKBzodHpXVxcOh2MwGOBLPzAw0N3d3dnZicPhiEQiVD40NITH48fGxuh0+sDAwOjoKLx+V1dXd3c3eg4N1Lt0On1sbIxAILS2tjY1NXGF5mKxWPAUuDg8PNzf3z86Ojo6OoqK5MPDw6Dvho84Ojo6NjY2MjJCpVKh5MjICOrDDxfhb/RgApPJpFKpvGP+3y54lMrD/0dxcbG3t/eePXtWrFhRUlIyYUql7/Cs5ISn1H71yu99xHfYsf9J8CiVh/+PJ0+e6Orq/vTTT5cvX/5Tgj/xwMP3Bh6lfsNgcwD5bcHqv47GxsanT59mZWXBCVSu+n+1AV9vw2+Uwn5LsfHvO+HfX2r5b2/z78Jv/ArfM74+nP4b4FHqfwe/kVK/foXrp6/X+U9Njy899DeqIMd3wp/Qpv/bY0wmk0wm81SiXPjP8ynCo9RvGmw2m0AgdHd3E4nE8d5OE5Zns9lMJpNEIkGKZjabzWKxWltb29vbxwf3g/JEIrGyshK8VidkZAqF0tnZ2dHRAfmix1cyMDAAbkackfEmBATcSk1NLS0t/brAS6VSm5qaPn36VFZWVlxc3NjYCOf3yWRyVVVVSUlJcXFxR0fHhE9ks9n9/f3p6el5eXkQmu9PmefsX44w1NbW3rp1KzExkac84QJ0NaT+/qfb8leBR6nfKlpbWyMiIq5fvx4UFHT37t3o6Oj8/Pzu7u4JbUoAII7h4eGkpKTdu3dbW1sjCEKj0U6ePOng4MDpUcSJsLCwdevWOTs7cwaX4kRPT09cXJyjo6Onp+ezZ8+4eASHw924cUNfX9/Z2RmM9V8BiURyc3ODuCRfL0mhUJKSkvbt27d69eotW7ZER0eDgb6rq8vDw0NXV3ffvn0ZGRlfCgKLxWI1NTVNTEz+xGhPKKU+ffpUTU3Nzc0NCB2Sb//qcvL94NWrV3D4+D8JHqV+kygpKdHT05OTkzt48KC3t/eFCxc2btwoISFx69at8bTFJYINDw97e3sLCgpqamqy2WwajXbw4EEzM7O6uroJn+Xi4iIgILBz5044QDm+ZojJsmrVqsmTJ2tpacGhT1T0S0pKmjlzpri4uJub2/gYoFxto9Fo169fx2Aw5ubmX3l9qLy3t9fKykpAQGDbtm2VlZWoKjMtLW3JkiW2trZfp8v79++/ePGCawH4kn72d6G3t7ewsLCmpgYqSUpKSk1N5Tqw/z1sgccD3ppOp/+HVSI8Sv32gMfj161bJy8vHx8f39vbSyKRBgcHS0pKtmzZ4uPjgzpOcoWIRkGn03Nzc5csWaKurg5CXH9/f29vL5rmmkajjYyMoIMeYpRs2bKlsbHxS/lUcDjc8ePHMRiMuLh4Wloa+tzBwcHTp09jMBgFBYW8vDxUzzgyMkKhULgENwhcHRcXJyEhgVIqnU4fHh7mbA8KJpMZExMjKSlpY2PDGdG1trbWyMgoIiICtJl0Oh3i54+OjoJeArQfQ0NDo6OjTCZzbGwMfEsZDAasMWNjY6iWg0Kh9Pf3Dw8PM5lMoAPwch0dHYWLUFVfXx/EpQXH0pGRERqNxmKxKisr169ff/bs2ebmZgqFAj6qEPmfxWJRKBSo5HcOAR7+veBR6jcGBoMRFBQ0derUs2fPclFSWVlZdXU1SII9PT3v3r3LyMjgEi3Ly8tfvXoVERGxePFiTU1NoNS2traqqirYOHd3d4eGhrq6umZmZvb09LDZ7E+fPqmoqOzYsSMrK+vly5e5ublEIpGLWPv7+yEoKgaD0dfXR09hPXr0SFlZGYPBaGhooOJzZmams7Pz2bNnU1JSULkVnuvg4HDo0CEhISErKysEQUgk0r17906fPv3zzz+np6dzhVtlMpkQTPr06dOc4bKwWKyVlVVcXFx7e/urV69u3rwZHx9/7949KysrLy8vIpHIZDJTUlKcnZ3fvn3b39+fkJBgbW19/fr12tpaOp3+8uVLBweH+Ph4Op3e1NR0/PjxpUuX7t69+8WLF3g8PiEh4cyZMwEBASdOnDA0NKyqqkpJSdHT0/vxxx+VlZUDAgLq6+v9/PxMTEyePn3a09Ojr6/Pz8+vpqZ24sQJe3v7n3/+2dXVNTU1FUEQKpWqp6d36NAhNHEAD/8B8Cj1GwOFQlm9erWIiAhMS/ZEmVHev39vYmJibm5+8uRJbW3t2NhYkIPc3d3XrFnj6OhoamoqKCi4du3agYGB8PDwVatW/T/2zjyeiv3/43PrtpeSLbJkXxPZsouQJWt2KkIiW9nKlovKVpItlaiUpZBElMi+7w5H9t2xb8c5HOb3x+fx9eh3b8ntqntvd55/1Zj5zGfmzLzm83l/3oumpiYKhWppaTExMVFVVb106ZKUlNSVK1fGx8dra2v5+fmJiYllZWUVFBS4ubn9/f1/N4Xv7+/39vaWkZERERHZt28fSLE6PT1tYWEhKSmpqqrKx8cH+vns2TMJCQljY2MTExMFBYWEhAQYhjs7Ow0NDY8dO3blyhUFBQUIgmxsbHA4nK+vLy8vb1RU1JkzZ1hZWX9XLWpxcRGk6bO2tgZFrgDgKmJiYkpLSy0tLSkpKbm4uFRUVNjY2MjJyQMCAsbHx11cXHbu3HnhwoXx8fHU1FQaGhpeXt62trbl5eVXr15JSkrGxsai0ehLly45ODg8e/ZMWVmZl5f3wYMHLi4uVFRUjIyMBw8eNDAwiI2NFRIScnBwePHihZiY2NmzZ8vLyy9evLh3794rV65gsdiEhAQKCgo1NbXs7Oz8/Hx1dXUWFhaQG6y/v5+MjMzS0hJJ4vczgUjqv4zKykoKCgomJiZQSgQYp3p6ei5fvnz69Glra2vwb2Ji4jt37qSkpLCxsYGXNjc3V0BAwMrKqqSkJCQkZNeuXUeOHMFisfn5+RwcHFxcXNXV1WB/Hx8fkJwUjDcbGxtBxpOIiIhbt26RkZEdPXr001EhDMM9PT0gyf/9+/dJSEjc3NxmZmbKysoMDAzc3NwuXrzIy8sLrJbXrl1TU1MrLS2NjY399ddfDQ0NZ2dn/f399+/ff/fu3a6uLk9PTwiCrK2t5+bmLl26pKenNz09fevWLQiCbt++/elJvySpaDT67NmzsbGxPT09MTExJCQkx48ff/PmTWhoKDMzs4aGxtjYWHl5OT09vYqKyujo6OjoqLa2NikpKajr5evra29vPzAwEBUVtWfPHg4ODh0dnX379oE6YLGxsfT09AoKCpmZmc3NzWlpaRAEnThxoqioKD8/PycnZ3R09OnTp9zc3E5OTgQCoaqqio6ODnwhYBi+ffs2OTm5v78/DofLyMhQUVEBmVURfhoQSf2XUV9fT0NDQ09PX1xcDP/PE7O3t1dTUxOCIAoKipqamry8vOjo6OTkZBsbG2ZmZhsbm/7+/pMnT3JxcVVUVMAw3NzcLCwszMvLC9q0sbE5evRoUVHRx48fU1NTX7x44e7uDsp+DA4ONjQ0cHJyKikpzc7OTk1NGRkZsbGx/S7pX29vr6en59WrV5ubm1lZWeno6Hp7e319fQ0MDIqKikxNTXl4eMDAtqOj4/nz54GBgZqamuTk5A4ODn19fdra2nJycmBd68OHDwwMDGfOnFlaWmpqagoPD/f399fW1v71119B6tiVhZ0VSbWxsQESD7Y3NTXp6OhER0cvLCygUCgODg43NzcYhtvb26WkpA4fPgz0V1paWkVFpa+vD4bhhISEvXv3mpqadnd3y8vLP3nyBIZhkGjKxMTE1tbW1dU1MDCwpqamvLyci4trJct1f3+/mpraL7/8wszM7OnpCabweXl50tLSly9fnpubAxUJL1y4ANyG6urqxMXFJSUlUSjUxYsXAwICflfXC+HfDiKp/zJmZmZYWFg2bdoE0lMBEcFisaGhoTt37pSWlgY1QpKSktzd3U+cOEFLS3vp0qXu7m4mJiZ2dvbq6moYhmtra0VFRfn4+JaXlxcXF/X19UVFRYuKiubm5jIyMq5cuWJoaMjDw3Pq1KnBwcG6ujoODg5ZWVngu+ru7n7gwAGgRCsASXV3dwelmzdu3Hjx4kU5OTl/f/+5ubkzZ84cPnwYGB/q6+vd3NyMjIysra11dHRCQ0N7e3tVVVUVFBRAmyCvqImJCR6Pf/PmzdmzZ8+fP29hYbF79+4HDx7A/19SwfKUpaXlSrgXuDoeHp6HDx8uLCxUVVWxsrI6ODiAU/Px8e3btw94AkhISKiqqoKUz21tbXJyclRUVNeuXdPS0gKJt62srPbt2wc+QvD/MkXl5eVxcHA4OjqCjVgs9sOHD66urqysrFu2bLG3t8dgMB8+fJCWlnZ1dQXVBsnIyGxtbUEiQSwWGxAQsGfPHiMjI2Fh4Xfv3v3Ea9//TRBJ/ZcxNzdnZGQEQdC5c+dWquwtLy/Hx8cTERGJiop2dXVdu3aNnZ09NTW1sbFRQUHBxcUFg8EICAhQU1MXFBTAMFxUVERHRyckJATD8OLioqKiooCAQF1dXXJy8r59+5ydnfv6+lRVVVVUVDAYDBqN5uTkVFBQGBgYwOFwHh4ejIyMv3PVHhwcvHbtGhi7dXR0cHJyQhCkrKzc1dWFx+MtLCw4OTnHxsYWFxfV1NQEBASAs7eCz1jq5QAAIABJREFUgsL58+c/fvwI8oQCU8bz58937dplY2PT1dUF0uBjMJjXr19TUFB4enrOzs5+GqGUk5NDSUkpJCT0qZ9jYmIiHR1dbm4uDMP19fUcHByXL1+GYRiFQh05coSGhgYMacXFxbW0tEB92fn5+ejo6A0bNpCSkkZGRoKVuhs3bmzevNnIyKiqqqq4uNjT0/Pp06cg7aG9vT04V1tbW0hIyNLSUmlpKQ0NDTMzc0NDQ0lJiYCAgL29PYFAAMVjTp06VVZWBkbHTU1N/Pz8EATp6OisVLdF+GlAJPVfxtLSUnFxsZSUFBUVVWBgYGdnJ/DgiYuL27x58/Hjx4eGhnR1dTk4OHJzcx88eEBNTa2hoVFWVubo6EhKSmpnZ9fU1BQdHU1ERERPT9/a2orD4ezt7WVkZOrr6728vCAIcnR0TExMZGdnJycnz8rKevv27YEDB3h5eRsaGjAYjJ6eHhkZWXV19aeuPw0NDaBa8vDwMIFAsLKyIiEhiYyMhGG4pqZGTk5u69atERER/f39vLy8wsLCGRkZPj4+EASxs7O/fPnS3d2dnJzcxMQkNzfX1NQUgiAVFZWMjAwFBYUjR46kpaVZWFhAECQgILBSiQSAx+PPnj1LREQEbMSlpaUJCQnGxsZWVlZgzScxMXHv3r2GhoYYDCY3N5eGhoaYmLiurq64uJiampqfn3+lEgwajWZjYyMhIWloaABbKisrT5w4sXXrViYmJj4+PjExsfz8/KdPn9LS0mprawOvhry8vB07doSFhRUWFoqKiurp6bW3tz969IiOjk5LS2tsbAyPx4uIiBw5csTb2xuUgIVhOCYmhpqaOjs7+z/omvrTg0jqv5KSkhJdXd2DBw/a29unp6dHR0dramoyMjKGh4cvLS15enpSU1NLS0tLS0tTUFDQ0ND4+Pi0tLScPXuWlpZWRUXl+PHj+/btO3DggI+Pz+joqIuLi4yMTGVlZWpqKjMzMwUFBScnJyg9b29vf/HiRRYWFgoKivj4+IqKCmpqaioqqps3b644RS0uLsbFxbGzs7Ozs8fGxoIlrzt37rS2ti4sLNy8eZOJiYmWltbU1BSFQnl5eYHVMCUlpcOHDx86dCguLg6DwVy6dImBgYGOjo6Ojo6amlpGRiY2NhYsKAkLC585c+bQoUMiIiJv37793a0YHBy8dOkSIyOjuLi4lJQUExOTlZVVV1cX+KutrS0tLS1YTXrw4AEtLe2hQ4cePXqkq6tLS0tLR0d3584dsOfo6GhISMjVq1dXAgTwePyHDx90dXX3798vISHx7Nmzvr6+W7duGRkZGRgYxMXFwTBcX19PT0/PwMDAwsJy5syZ1tbW1tbWq1evnjp1yt7ePjc3F4vFRkZGnjp1Kjk5ecXpDZSe/VI0GsK/GkRS/5WAwPns7Ox79+4lJSXFxcU9fvy4oqICyFx/f39iYmJiYmJdXd27d++ePHkChlRdXV3Pnj0LDQ1NS0srLCzMzc0dHx/H4/HW1tbS0tIFBQU4HK6wsDAmJqasrKyysjI7O7u7u/vNmzeRkZF37typrq7u7+8PDw+/f/8+qGcHOjMzM1NdXf3y5cuXL18WFxcDn3ksFgsqoY6NjfX09PT19Q0PD+NwuOnp6d7e3o6ODpAEur+/H/R5cnKysrLyw4cPKBSqv79/YGBgenp6dna2p6enq6sLg8EMDg4ODAzMzs5+Gm4A/jE9Pd31P9rb21e8EUCCgt7e3sHBwZmZmampqd7e3v7+/snJyb6+PpCXYHx8HDiiLS0tYbHY2dlZ4NIPWgBpp7u7u4HRg0AgTExMjI2NDQ8PT0xMgLiAvr6+jo6OtrY2MK/H4/Gjo6NjY2MgQAA0Ozo6uhJW0NLScvXqVTc3N6QOyk8JIqn/biYnJ0Gq+RWBWwkSXQlv/1290qmpKeDPNDs7Ozg4ODo6ys/PD8qs/m5/0BQOh5uZmZmdnQVaCfLSz8/PA2kD4Ul4PB7EEc3Pz39qEPgeE9tPQzlXT62yxrN/mkHqzx64lt1WqKio0NfXZ2JikpOTq62tRRamfkoQSf2PMjc3Fx0dzcvLKygoyMPDk5WV9W1hkZ+VlX+jiXAVmV5dc7904B/bycvLk5GROXLkSGxsLJJF5WcFkdT/KDgcLjMzU0NDw9jYGFSl/rt79DMDVBiDwRQXF9fU1KzUvEL4+UAk9b8LgUDo7e1FoiF/AH80JvwbB/IIawGR1P8oyBv+I1n+HH93pxC+C4ikIiAgIKwbiKQiICAgrBuIpCIgICCsG4ikIiAgIKwbiKQiICAgrBuIpCIgICCsG4ikIiAgIKwbiKQiICAgrBuIpCIgICCsG4ikIiAgIKwbiKQiICAgrBuIpCIgICCsG4ikIiAgIKwbiKQiICAgrBuIpCIgICCsG4ikIiAgIKwbiKQiICAgrBuIpCIgICCsG4ikIiAgIKwbiKQiICAgrBuIpCIgICCsG4ikIiAgIKwbiKQiICAgrBuIpCIgICCsG4ikIiAgIKwbiKQiICAgrBuIpCIgICCsG4ikIiAgIKwbiKQiICAgrBuIpCIgICCsG4ikIiAgIKwbiKQiICAgrBuIpCIgICCsG4ikIiAgIKwbiKQiICAgrBuIpCL8VCz/j7+7Iwj/URBJRUBAQFg3EElF+O7Mz88PDg5iMJipqamlpaXveqLu7u7W1tbe3l4CgfD9ToSA8CUQSUVYH8Bce35+vqioCIVC4XC4lT9VV1fr6uoaGhrevn17YmJi9UZAOzgcbnZ29s9O4ZuamrS0tPbu3SslJTUyMvKtl4KA8O0gkoqwPgDt6+rq4uPjMzU17evrW/lTZWUlPz//tm3bdHV1h4eH19JacHCwra3tn+3DxMSEo6MjBEGkpKSDg4N/9nAEhL8OIqkI68bMzExERAQEQTt37iwqKlrZXlNTIygoCEGQhobG6OjoV9spKSlhYmKSkZH5hj4kJSVBEERBQYFIKsLfAiKp34v/4Lpze3s7Pz8/BEEQBIWEhMzNzYHt/f3958+f37RpExcXl4WFha6urre3d3NzMwzDi4uLWVlZOjo6CgoKqqqq2dnZGRkZ8vLyEASRkJCYm5u/evXqwoULOjo6vr6+Dx48sLGxsbS0rKqqmp+fDwsLMzc3P336tLa29sOHD6empmAYfv36NQRBVFRUg4ODHR0ddnZ2ysrKT548+a42XASEFRBJXX/Gxsb6+vr+a5KKw+HS09M5ODj27t27YcMGDQ2Njx8/gj/NzMz4+flt2LCBjIzMzs6OjY1ty5Yt5ubmvb29NTU1fHx8dHR0Tk5OgoKCt27diouL4+bmhiCIhobG29u7qKjo9OnTYOTLxcUF9NrHx+fmzZvU1NSSkpIGBgabN29mZmbOy8uDYTgtLQ0cOzo6+vLlywMHDigpKb19+3Zpaek/9XMg/F0gkrr+jI6O9vT0/N29+HEAqWppaXF1db19+/bFixf37Nmzb9++9PR0sMPk5KSXl9fGjRuFhIQ6Ojri4uL27t1LRET05s2b5ORkCIL4+PjS09OLioqam5vr6+vV1dUhCFJUVASHp6en79+/H4IgbW3ty5cvX7t2LT4+3tDQ8ODBg9HR0TExMczMzBAEBQQEgJ0hCKKkpMzOzj5z5szVq1cxGAz8n5w0IPwtIJL6vfiPvMMrl/ns2TNubu779+97eXlt374dgiBra2uw7D49Pe3j47N161YtLS0MBtPS0iIsLAxBUGBgYENDAwsLC5iqBwYGDg0NodFoJSUlCIKUlZXBKRISEigoKCAIevbsGdiyuLiYk5Pj6urq5OSkqKi4Y8eOHTt23Lp1C/6fpG7btk1SUnLbtm1xcXG/6ycCwncFkVSEb2d5eRnYKIeHh+3s7BgZGc3MzAwMDJiYmDZt2kRDQwNEcHh42NbWdsuWLVpaWkNDQ83NzSIiIhAEOTg4wDAcFxfHwcEBZvQuLi7v379XUVGBIEhVVRWc5fnz50BSY2NjwRY8Hl9dXX3+/PlDhw6dOHGCnJycmZk5KysL/p+kbtiwYe/evRAEHT9+vKSkBAmpQvhhIJKK8O2sSGpsbKysrOyzZ89qamo6OzufPXvGyMgIQdD58+fxeDwKhRIREfnll19UVFTGx8crKipYWVnJyMhSU1PHxsYyMjLS0tLExcUhCBITE0tMTNTX14cgSFpaemRkBIvFxsfHk5KSQhD06NEjcN7W1lY1NbXNmzcfO3bM19eXiYmJnJz86dOn8P9sqURERN7e3ry8vBs2bDh58iRYCkNA+AEgkorw7YBx39DQ0MmTJ48cOTI5OQm29/T08PHxQRBETU39/PnzxsZGMCxlZWWtqKhwdnbesmXLqVOn8Hh8amoqBwdHdHR0QEAAOTn5hQsX5ubmrl69umHDBnJycjc3t7KyssDAQBISEgiC7t69u7i4CMNwfX29hIQEWIbi5+cnJibesGGDpaXl5OTkgwcPIAjat29ffn5+VFQUFRXVr7/+6u3tPT8//3feKYT/DIikIvxV/P39t2/fTkZGFhYWBrYUFhauzOW1tbVTUlJOnTrFw8Nz6NAhDg4OCgoKAwODmpoasKeQkBAHB8eBAwfExcWLi4thGM7JydHT05OWlvb39+/o6LC2tpaWlpaRkXFycmpsbIRheGBg4Nq1azIyMsrKyvHx8Z6enuLi4nfu3GlsbHR3d5eWllZVVY2IiLh7966enp6IiMi5c+fKysr+xluE8N8BkVSEbwdM/BsaGjIzM3NychobG4HJcnh4uKio6N27d2/fvi0vL+/r60Oj0bW1tRUVFWlpaVlZWV1dXeDYmZmZurq6rKys9PT0urq6hYWF5eXl2dnZzs7OxsbGgYGBhYWFpqamxsbG5uZmFAo1Nja2tLS0sLAwNDSEQqFaWloWFxfHxsaampqGh4cnJibQaDQKhWpubm5ra+vq6mptbW1qakKhUBgMBrGlIvwAEElF+Ev8FZ36tmMRZUT4J4NIKgICAsK6gUgqAgICwrqBSCrCf461uKkuf8IP69gqffi2zoBDQDDu97iWH3NzftfzT//7D7QCIZKKgPBF/nZJ/V1qgr9ouf5O17KwsPBdE36vpLwBJ/qdpOLx+Pn5+X9OWhxEUhH+EgQCYWZm5tOE06uwsLAwMTGxsLDwvXv1JcAbODU1NTIy8qU+4/H40dFRDAaDxWL/9mQry8vLBAJheHi4u7sbh8P92c7gcLj+/v6enp7p6envcS0YDCY3NzcnJ2ctORu/maWlpe7u7rdv3xYWFgLf55ULWVpays/PT0xM7O7u/n4d+FP8hJK6uLg4NTU1MTExOzs7Pz9PIBA++zAtLy8vLCzMzMzMzMwA353P7oPD4fr6+srLy/F4/Pfo7T98FvMlQFcXFhbS09O9vLw+fPjw1Z1nZmYSExMtLCxqa2t/UC//wPz8fF5e3uXLl01MTOrr6/+4w9LS0rt37wwMDHR0dAoKCn58Dz9l5b45ODhISEh8QwxYc3PziRMnmJiYYmNjV//sffoc/m4kuArXr18nJydXV1dvaWn5s31bO3g8XlFRkYSE5Ny5c7+TzoWFBW9vbw0NDZCHbHV+zPv1s0nq5OTkkydPTp48eezYsXPnztna2gKX8s/ezdLSUg0NDRkZmdevX3+2tfn5+YiICHZ2djExsfHx8e/R4ZWYzi918p/M+/fvRURE6OjoHj9+vPqeBAIhNzdXUFBw27Zt2dnZP6Z7f2R+fj4qKoqSklJISOizyr64uBgcHExCQkJLS/vq1asf30PA0tISGo0GRWVwOFxkZKSNjc03pDfr6enR0dHZtGlTSEjI6vFjK89eV1dXeXn5GttHo9H8/PyCgoJNTU1/tm9rZ2lpKSoqioSERE1N7Xc3YXl5GXg9g2y5/wR+KkldXFwMDw8/cuRIWFhYWlqak5MTKSkpeNs/q1YDAwNSUlLExMQpKSmfbZBAIDx79uyXX34hIyMDOeK+E7W1tVVVVd+v/e9Ef3//iRMn9uzZEx0dvfqey8vLaDT66NGjEARlZmb+mO59lubm5uPHj8vJydXV1f3xr8vLy+3t7Tw8PKSkpF/60P4AiouL9fT0SktLwX9nZ2cxGMw3zJMIBEJ0dDQZGVloaOhaQnK7u7t9fHxu37791T1XXih9ff3vLakwDDc3Nx88eFBTU/MbXsOpqamSkpL29vbv0bE/8lNJanV1NQh5BP/t6Ojg4+N78OAB/OUBoImJCSsr6yrRilVVVaysrPT09J9+Br+6fvpnlwIuX77s7u6+yg7r4lG/tLS0RqPnKidtb29vbGxceb1v3LjBzc2dmJgIw3Bzc/OnNrXBwcHy8vKWlpaZmRkYhnE4nKen565du9LT00GYE+jMGu/V9PT07Ozs3Nxcf3//Sk1AFApVWlpaXV2NxWJhGF5YWBgYGABmn/T09NbW1k9bKC8vj4qKSkpKkpWVPX78OBilDg4OxsTEhIeHV1ZWrlyUrKzs/v37IyIiEhMTnz9/DiYoWCz248ePMzMzHz9+jImJiYmJ+fjx4+zsbHp6ekRERERERG9vL7g/Dx48ACPcmZmZ1NRUPz+/wMDAkpKStWji8vJyRUWFlJTU9u3bjY2NW1tbh4aG4uPjc3NzCQRCS0tLSkpKUlJSdnZ2bGzsjRs3QAgvIDMz083NzcTExMfH5+7du3Fxcf39/UVFRZSUlKGhoaDlwMDAxMRELBaLw+GioqJUVVVNTExiY2Onp6fr6uoMDQ2pqKi4ubnDwsLQaPRafhd9fX0BAYG+vr6uri4TExNtbe3MzMzl5eXJycnffvtNWVn55MmTN2/eBGFsd+/edXJy8vPzs7CwOHny5J07d7Kzs3/77TddXV0vL6+Ojg4YhqempkJCQkxNTR0dHS9cuFBdXQ2+x3x8fJycnKdOnVJTU7O0tMzLy5ufn8/KynJycvLw8GhraxseHgbpeq9evWpiYmJgYNDb25uUlKSvr6+hoaGurv7w4cOFhYXU1NRLly5ZW1s7OzufOnVKR0cnNDR0HZfXfipJzc/PZ2FhoaKiysnJAVuysrJWLFD19fVeXl6Wlpb3799feSednZ2lpKSAcQCG4dzc3EuXLp07d+7+/ftAHaqqqvj4+KipqZOTkwMDA69evbpiSVhdUmEYHhwcjI6ODg0NdXBwCAsLGxgYWF5ezsvL8/T09Pb2vnnzZltbGwzDsbGx+/fvp6GhCQwMLC0tvXv37rVr14aHh2dmZkJDQ69evVpbW/vVhxuPx+fm5t68efP69evBwcGurq4ODg4vX76E/zfyun//flBQkL29vY+PT3Nzc1dXV3h4uLe397179y5evGhvb3/v3r2xsbGqqio7Oztvb++cnBw8Hj88PHzz5s2wsLDx8fGhoaHQ0FBra2tLS0t7e/vKykoYhqOiovj5+RUVFQ0NDcXFxS0tLYGyFBcXOzo6nj59Wk9Pz9vbe3JyEovF+vr67tmzR1JSUklJ6ejRox4eHs3NzV+V1MXFxaSkJBMTExMTE11dXRkZGR8fHywWm5SU5OTkdOPGDXNz89DQ0NLS0tu3b588edLIyOjMmTNiYmLq6up5eXnArvLixQsFBYVz585ZWlqCPrS0tLS3t1+5ckVLS8vIyEhVVTUsLAyonqys7Pbt248dOyYtLc3Ozh4cHDw5ORkeHq6urn7mzJmzZ89KSUnR09O7uLiMjY2FhoaysLBQUFDk5+fDMFxeXq6iomJjYzM6Ourl5SUvL+/n56ejo3Ps2DGQfnB1lpeXs7KyaGlp9+3bp6GhgUaj8/Ly2NjYDA0NCQTC69evpaSkmJmZFRUVzczMODg4NDU1u7q6FhYWsrOzJSQkzp07Z2dnx8PDQ0VFdebMmfb29oqKCmpq6nv37nV2durr68vKymZmZra3t7u5uXFyclpYWCgqKnJychYWFqLRaB0dnY0bNwoKCiYkJICg4a92WE9PT1JSsrOz8+HDh3v27Dl9+nRRUdHIyMiVK1c0NTU9PDyOHj26Y8cOOzu7Dx8+nD59etOmTcLCwlZWVkJCQnR0dNra2mfPnmVmZiYmJr5//z4MwyEhIVu3bj1x4sRvv/3GzMzs4eExMzODRqMPHz68a9cuIyMjDQ0N8L2ZnZ0tLi4+fPgwAwNDTk7O2NiYjY3Ntm3baGlpZWRk5OTkXr58eejQIWlp6SdPnigqKnJzczc3N6enp4MUvXp6em5ubrS0tAcPHlzHMexPJakYDAakOmZjY4uOjv7Ukl1UVKSrq6uoqKikpMTBwXHr1i2wdBgeHn769OmqqioCgfDhwwdhYWFxcXFtbW0BAYHAwMD5+fmqqipeXt69e/fa2NgoKSlt2LDB3d0dzKFWf+BwOFxaWtqJEye8vb21tLT4+PjAkqWAgIC8vLyNjQ0bG5uHh8fk5OT169eJiIjo6Ojc3NxycnI0NTU3bdpUW1s7PT2tpqZGREQUFRX11WvH4XBxcXGsrKwQBB05cuT48ePbtm1jZWWtrKycmZlxdXXV19e3t7cH2UycnZ3z8/PFxMQgCFJSUtLV1aWhoeHh4SkrKystLT1w4AAEQTdu3MDj8c3NzSwsLIaGhsPDw3fv3uXn57e2tjY2NoYg6NixY/39/Y8fP2ZlZeXl5T158qSwsPDmzZuvX78+MzOjqanJxcUVGRmppqZGS0tbW1s7Nzfn7e29e/duXl5eHR2dgwcPQhDk6ur61UtbWFiIjY0F2QK5ubl1dXVDQkIKCwv5+PjOnTsXFhZ28ODBvXv3enl5ubu7b968mYKC4sKFC1euXNm2bduVK1dgGK6qqpKUlJSTkyssLIyPj6enp5eSkmpvb3/48KGEhMTTp09fvnxJTEwsKCgIvrUyMjIUFBR2dnY3btxgZWU9cuTI+Pj43bt3N2zYADIWhoeHs7Ozc3JyotHoxsZGOTk5CIJAFYM3b96oqqrevXsXjUZLS0ufO3cOhmFvb28Ignx9fb96sTAMd3R0aGtri4mJxcfHLy4uFhUVMTMzS0pKwjBcV1cnKiq6fft2S0vLt2/fmpub09LSxsXFjY6Onjp1asuWLcBWoKGhAUEQeFArKiooKCjOnz/v4eFhbW2dnJwMw3BnZ6eNjY2jo+Ps7OyNGzc2bdoUHx8Pw3BiYiIHB4eHh8da+gkwMjJiZ2f38fFxcnKKiYkBqcIyMzNJSUklJCTA6uWOHTtkZGS6u7vDw8P37Nlz+fJl8EVkYGDQ1tZGoVCpqank5OQuLi4LCwvBwcHa2toFBQUZGRkiIiIGBgajo6Ojo6PCwsLgho+NjcnLy/Py8oKpyYULF4SFhYGB/tWrVwcPHlRSUqqpqWlvb6+srLS3t4+Pjy8vL1dVVd2/f39OTs7c3JyRkREbG9u7d+9gGHZ0dGRiYiosLFz7Ja/OTyWpMAz39vZevHiRjo5u8+bNRkZGubm5YHYZHR2trq7e0NDQ1NTEwcEhJiYGRq/BwcF6enp1dXU4HC4iIkJGRgaNRk9OTgoJCYmLiw8MDLS3t8vLy5OTk8fFxZWWlnJyciopKYGqSqtL6sTERGBg4LFjx4qKimZmZh49elRdXR0XF6esrFxTU1NbWyshISEtLY1GowcHBwUFBU1NTWEYJhAIt27doqSkBJa+sLAwERER8PX+KkNDQ4aGhnR0dDdv3uzo6HBzc9uxY8eFCxfy8/PZ2dltbW0jIiJ0dXW3bdumpaVVVlZ2/vx5UlJSkGY0JiaGn58fGEkSExNpaGi8vLwWFhbevXunpaVVVFTU3t5+/PhxPj6+O3furHzbm5qaHj9+fPDgQZCDqqamhouLi4ODo6WlxdPT09XVtayszNjYmI6OrqCgYG5u7vr167t3737+/DkMw1lZWWRkZMLCwmu0jrm4uDAzM4NjFxcXPT09KSkpw8LCUlJSDAwM2NjYnj59WldXJyIiYmlpCQ7h5OTU1NQcGxtzd3enp6cHttHJycmTJ08eP34chULl5OTcuXPn/fv3kZGRjIyM/Pz8YI4vKSkpIiLS2dm5tLRkYWHBxcUFfms5OTkeHp7q6moYhp2cnGhoaHJycpaWltLT04mJie3s7MbGxnx9fdXU1Hp7e8fGxp48efL48eOUlBQtLa0dO3YEBQWtfo3gLOPj42ZmZkpKSg0NDTAM9/X1qampSUhIwDA8Oztrbm4uKioKrBb3799nZGQMCgoaGhrS0NDYtWsX6JuOjs7OnTuBetbW1u7cuXPPnj1MTExgYgHD8NLS0sjIyOvXrwMDAzU1Nbdt25aWlgbDcFJSkri4+BqlH2BmZgZB0O7du8+fPw+2LC4u/vbbbzQ0NHx8fJaWlr6+vjdu3Hj+/Dkej3/58iUlJSX4EV+8eCEhIQHOhcFgwKh/dnZ2amoqLS3t5s2bpqam7OzsZ8+eBTY3KSkpFRUVDAYzNzdnZWXFxsY2OzsL/2+i+ebNGxiGP3z4cOzYMQcHh5WJfHl5+dWrV62trQ8dOsTAwJCXlzcxMWFpaamoqAjulbOzMzMz84rZ+q/zs0kqDMMEAiE5OVleXn779u1MTExpaWkLCwu9vb3Z2dk5OTn+/v5sbGxycnLA7cPDw0NeXr6mpoZAILS2tj5//jwlJSU6OpqRkVFBQaGnpweLxTo7OzMyMoLxi6ioKCsrK5jirQ4Oh3v27BkDA4OoqGh0dDSogYzBYEpKSjIyMlxcXFhYWI4fP/7x40eQXfTMmTMwDOPx+KCgoBVJvXXrlpCQEFC6rzI/P29nZycjIwO8f3Jzc7m5uUVFRa9fvw7y6bm6ujo7Ozs6Oj59+rStre369euMjIzDw8MwDJe